Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Discovery of a novel Lactiplantibacillus phage enhancing flavor compound production in high-temperature Daqu - Yuhua Yao; Yabo Li; Meina Jiang; Yuting Sun; Xiaowei Zheng; Yansong Xue; Bei-Zhong Han (Food Microbiology, 2026)

Methylparaben promotes colorectal tumor growth through nuclear receptor–mediated transcriptional reprogramming and inflammatory signaling: Evidence from integrated transcriptomics and network toxicology - Zhisheng Ma; Zheng Zhang; Yao Zhou; Zhaoyu Song; Xinyue Wang; Peifeng Chen; Wannian Sui; Jiajun Qian; Along Li; Maoming Xiong; Guodong Cao; Wenxiu Han (Food and Chemical Toxicology, 2026)

The effects of spark plugs and lubricant oils on pre-ignition combustion in a hydrogen fueled engine - An Lu; Peng Yin; Benzheng Fan; Kuicong He; Xiaogang Yang; Yuan Bi; Xiaowei Hao; Yao Li; Huimu Yang; Dong Han (Fuel, 2026)

Biological and genomic characteristics of a polyvalent Salmonella phage and its dual application in food decontamination and chick salmonellosis treatment - Xinyan Yao; Sijia Luo; Jinghao Xie; Chaoxiang Jia; Yingqian Han; Yanbin Yang; Yueting Zheng; Jiajia Pan; Juan Geng; Yueying Wang; Heping Li (Food Research International, 2026)

Genomic and food-safety evaluation of Staphylococcus chromogenes in Chinese dairy milk - Xiaoping Li; Baoling Zhang; Tao Zhou; Moli Li; Kai Chen; Shu Li; Xiaofang Tong; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Yuqiong Li; A Yao; et al. (Food Research International, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Construction of cost-effective catalyst from retired power batteries and natural mineral toward catalytic oxidation of VOCs - Haoxiang Liao; Yao Xiao; Chaoya Han; Zhi Li; Taoli Huhe; Xiazhang Li (Applied Clay Science, 2026)

Modeling of hydrological performance degradation in permeable pavement systems induced by their spatiotemporal clogging evolution - Zihao Liu; Qiongfang Li; Yiqun Sun; Zhengmo Zhou; Yao Du; Shuhong Xu; Xingye Han; Xing Huang; Junliang Jin (Journal of Hydrology, 2026)

Enhancing second-stage dipleg discharge in series cyclones via interstage introduction of Geldart Group A particles - Li-Xin Yang; Jian-Yi Chen; Han-Gong Zhang; Kang-Shuai Liu; Yao-Dong Wei (Journal of Environmental Chemical Engineering, 2026)

Unlocking efficient Li recovery from spent LiFePO4 batteries at high pulp density: Passivation release mechanism of Fe3+-mediated biochemical synergistic leaching and life cycle assessment - Ziyun Liang; Jinghan Gu; Xin Zhao; Lang Yun; Shenghan Li; Zaiyu Li; Wenyan Liu; Jiali Wang; Yao Wang; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Development and validation of a sensitive sandwich ELISA for quantification of insulin-like growth factor 2 in goat milk - Yao Wang; Jing Liu; Yinting Hao; Jingyu Gong; Yaxian Shang; Mengdi Han; Dekun Chen; Jia Li (International Dairy Journal, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Unraveling the promoting role of Fe in NiFe bimetallic catalysts for enhanced low-temperature CO2 methanation - Zhuoyi Yang; Ruwei Yao; Meng Yang; Han Zhang; Yueyin Song; Qinqin Niu; Congming Li (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Color-tunable and multi-stimuli-responsive room temperature phosphorescence based on an efficient supramolecular approach - Huan Yao; Yu-Ling Hu; Jun-Fu Chen; Han-Yu Luo; Wen-Jie Chen; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2026)

Geological hazard susceptibility and segment-based risk assessment of mountainous expressways: A case study of Lianying Expressway in Guangdong, China - Yao Niu; Zishuang Han; Zhiyuan Li; Manchao He; Zhandong Su (Transportation Geotechnics, 2026)

SIRT7-mediated H3K79 desuccinylation modulates functional activities of goat ovarian granulosa cells - Yawen Li; Lei Wang; Shuaifei Song; Qiuyan Li; Ying Gong; Zihan Wang; Shiyi Yao; Zihan Ma; Yingping Xia; Cong Zhou; Xinyang Yao; Jia Luo; et al. (Theriogenology, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Spatial information preservation and semantic feature consistency for urban sewer pipeline health detection with sonar image - Jun Li; Qingbang Han; Chaoqun Teng; Yao Huang; Ziang Zheng; Jinming Liu (Journal of Water Process Engineering, 2026)

Nitrogen metabolism and microbial responses in anammox under dual stress of N,N-dimethylformamide - Yujie Hua; Anni Zhang; Xiang Li; Yan Yuan; Yayi Wang; Yao Xu; Han Wang; Yong Huang (Journal of Hazardous Materials, 2026)

Decision-making for enhancing thermal resilience: Identifying and prioritising intervention domains across social, economic, ecological, and technological systems - Xizhen Huang; Runming Yao; Shiyu Han; Christos H. Halios; Eugene Mohareb; Prashant Kumar; Baizhan Li (Journal of Cleaner Production, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Inactivation of Staphylococcus aureus on eggshells by combined slightly acidic electrolyzed water and UV: Influence factors, mechanistic insights, and penetration risk evaluation - Yitian Zang; Yao Zang; Yingjie Feng; Mingming Tu; Haojie Zhu; Jiahong Han; Shan Bing; Yanjiao Li; Xianghui Zhao; Nengshui Ding; Guoyun Wu (Food Control, 2026)

Antibiotic resistance genes (ARGs) in rice: Source attribution and putative mobility patterns - Jie Hou; Ye Li; Mengqi Liu; Linyun Li; Hongan Chen; Yi An; Han Xu; Yanpo Yao (Food Microbiology, 2026)

Benchmarking backbone neural networks for HVAC fault diagnosis and regression: Insights into spatiotemporal, graph, and attention-based architectures - Zhe Sun; Peng Yang; Ling Shi; Qiwei Yao; Lin Li; Han Xiao; Xiangwei Zheng; Xi Shen (Energy and Buildings, 2026)

A synergistic piezo-photocatalytic strategy via BaTiO3 heterophase homojunctions for MRSA-infected diabetic wound therapy - Lei Qian; Han Lin; Min Wu; Zheng Fang; Jiawei Li; Yao Han; Jinxia Zhai; Peng Yu; Cairong Xiao; Chengyun Ning (Chemical Engineering Journal, 2026)

Fucosylated human milk oligosaccharides: A comprehensive review from structure and function to biomanufacturing and industrial perspectives - Mengli Li; Jiawei Yao; Ruoyu Jia; Mo Han; Ming Miao; Tao Zhang (Carbohydrate Polymers, 2026)

Photochemically corrected machine learning framework for real-time VOCs source apportionment in support of air quality management - Yu Han; Xing Peng; Yi Hong; Jiang-Yao Tan; Jiang Wu; Li He; Xiao-Feng Huang; Guang-He Yu; Ke Du (Atmospheric Environment, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

A multifunctional fluorescent sensor for sequential off-on-off visual detection of Zn2+ and glyphosate in food and biological matrices and efficient removal of Zn2+ from aqueous media - Xiao Han; Yao Li; Xinyi Tan; Wenlong Qin; Haiyan Xu; Chuanxiang Chen (Analytica Chimica Acta, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

Impacts of concentrated leachate recirculation on methane production suppression, odorous gas emissions, and salinity accumulation in municipal solid waste - Yu-Xiang Zhang; Xuan-Qi Zhang; Wen-Jie Xu; Han Ke; Ji-Wu Lan; Yun-Min Chen; Tian Qi; Yao-Huang Li; Xue Cai (Waste Management, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Polystyrene microplastics trigger intestinal inflammation through CXCL11-mediated T-cell recruitment - Yao Tan; Xiaoyan Chen; Hao Ge; Yu Han; Binqi Yang; Xiaopeng Zhu; Li Yuan (Journal of Environmental Sciences, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

Unveiling the flavor and microbial dynamics: a comprehensive analysis of key flavor compounds and core microorganisms in industrial-scale naturally fermented Jianshui pickle - Wenwen Zhang; Wenwen Li; Yu Qin; Xing Han; Dengjie Yao; Muxi Yang; Lirong Li; Rui Huang (Food Chemistry, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Numerical Ecohydraulic Modeling of Fish Habitat Conditions in Braided Rivers: The Role of Multi-Threaded Structures - Ruida Wang; Lijian Ouyang; Shicheng Li; Ayong Jiao; Chenyang Cao; Hao Zheng; Xiaowei Han; Shengzhi Zhou; Gang Xu; Xinggang Tu; Weiwei Yao (International Journal of Environmental Research, 2026)

Sodium nitroprusside improves photosynthesis and antioxidant properties of sugar beet to alleviate salt stress - Jingjie Chen; Xiaodong Li; Pingan Han; Xiaoran Zheng; Gui Geng; Jiahui Liu; Maoqian Wang; Yao Xu; Yuguang Wang (Horticulture, Environment, and Biotechnology, 2026)

DPA-MSCL: A multi-scale supervised contrastive learning method based on dynamic prototype alignment for lithology identification - Xianshan Li; Saiwei Sun; Yao Wang; Ning Shi; Pengwei Zhang; Chao Han; Yurun Shao; Hongjia Ren; Fangfang Pan; Fengda Zhao (Earth Science Informatics, 2026)

Ubiquitin-mediated downregulation of the proteasome subunit ADRM1 mediates in vitro capacitation of bovine spermatozoa - Lipeng Cao; Chunyu Li; Yue Han; Yanqiu Lv; Jie Wang; Xinglin Qu; Yuyang Zhang; Weiyu Gu; Qinglong Xu; Shunfa Yao; Jinwei Lu; Aihui Lv; et al. (Animal Reproduction Science, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Nano-sized carbonates in lake sediments: a novel archive for unlocking past environmental changes - Xianming Zhang; Xianqiang Meng; Yilan Liu; Li Huo; Han Zhou; Zhenyu Ni; Weiwei Sun; Yao Wang; Enlou Zhang (Science Bulletin, 2026)

Environmental and economic assessments of novel polyurethane prepolymer modified porous asphalt: A case study in Hong Kong - Gaoyang Li; Jun Wang; Linyi Yao; Bin Yang; Guoyang Lu; Meizhao Han; Fuliao Zou; Zhen Leng (Journal of Cleaner Production, 2026)

Substrate source and mineral protection synergistically govern the temperature response of lake sediment organic carbon - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Min Cai; Bingfu Yao; Li Liu; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Jianping Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Impacts of WRF-based Precipitation Quality on Urban Flood Simulation Accuracy - Shuhong Xu; Qiongfang Li; Zhengmo Zhou; Yiqun Sun; Xingye Han; Qihui Chen; Yao Du; Zihao Liu (Water Resources Management, 2026)

A precise global ionospheric total electron content forecasting model based on multi-neural network ensemble - Huan Zhang; Yuanyi Han; Mengzhu Peng; Bao Zhang; Chaoqian Xu; Cheng Huang; Feifei Tang; Jian Kong; Yibin Yao; Jianping Pan; He Huang; Hongming Li; et al. (GPS Solutions, 2026)

Plant-derived extracellular vesicles: multifunctional nanocarriers bridging food bioactivity and therapeutics - Zeqian Yang; Shuyuan Shi; Boqing Yao; Zixin Han; Ruiyun Wu; Pinglan Li; Nan Shang (Critical Reviews in Food Science and Nutrition, 2026)

Study on the mechanisms of action of Ephedra sinica Stapf extract in treating acute exacerbation of chronic obstructive pulmonary disease (AECOPD) - Zhe Li; Gui-yun Qian; Ye Yao; Mei-yan Wei; Wei Han (Natural Product Research, 2026)

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Detection of critical pollination growth stage in maize based on improved YOLOv8s - Dong Wang; Han Zhang; Yao Wang; Peng Song; Xingyue Li; Kai Kang; Bin Luo (Computers and Electronics in Agriculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Synergistic remediation of cadmium-contaminated soil by polysaccharide-producing bacteria and organo-Fe hydroxides co-precipitates: Mechanisms of immobilization and soil structure improvement - Shuangjiao Tang; Yun Li; Nannan Zhai; Xiaochong Wang; Randa S. Makar; Wenxia Wang; Lunguang Yao; Zhaojin Chen; Hui Han (Journal of Environmental Chemical Engineering, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Liquid metal microspheres enabled photothermally triggered shape memory fibers with strong thermomechanical interfaces for soft robotics and actuator-sensory hybrids - Zifeng Wang; Yunyao Tang; Yu Wang; Qingzhu Huang; Dehui Li; Zhenxia Ma; Zhuo Shi; Yu Yao; Zhuoyun Jiang; Yutong Han; Zhigang Zhu (Chemical Engineering Journal, 2026)

Silicate-mediated interfacial switching enables simultaneous removal of Cd(II) and TBBPA by ferrous sulfide - Kaipian Shi; Li Yin; Jinyu Han; Youru Yao; Yong Zhang; Huan He; Shaogui Yang; Shiyin Li (Chemical Engineering Journal, 2026)

Response of soil humic substances to snowpack decline across different soil layers in the subalpine forest - Li Zhang; Wenlan Huang; Yao Liu; Sining Liu; Han Li; Bo Tan; Chengming You; Hongwei Xu; Lin Xu; Zhenfeng Xu; Yalin Yuan; Jiao Li; et al. (CATENA, 2026)

Liraglutide Promoted Osteogenic Differentiation of Dental Pulp Stem Cells via H3K18 Lactylation-Dependent DSPP Activation - Ruixue Li; Jing Zhang; Xixi Song; Lulu Han; Mingyan Yao (Tissue Engineering and Regenerative Medicine, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Allelopathy enhancement of an invasive potassium-rich plant Alternanthera Philoxeroides by potassium fertilization is caused by the increase of allelochemicals and potassium concentrations - Bing-Yao Li; Yu-Han Xiao; Wen-Qi Duan; Hong-Yu Xiao; Yan-Hong Wang; Mohamed Abdelaziz Balah; Ai-Ping Wu (Plant Ecology, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Age- and season-modulated water use strategies in mixed plantations of Betula alnoides and Castanopsis hystrix - Yu-han Chang; Bo-yao Chen; Chun-sheng Wang; Kai-li Liu; Hai-feng Yin; Jie Zeng (Agricultural and Forest Meteorology, 2026)

KDM3A Modulates Trastuzumab Resistance in HER2− Positive Breast Cancer Cells via the PI3K/AKT/ERK Pathway - Yuanxing Han; Jiayi Guo; Ting Yang; Xuewen Liu; Honghuo Yan; Yuanzhang Li; Juan Yao (Biochemical Genetics, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Phylogeny and Taxonomy of the Coral Reef Maidenhair Fern Adiantum capillus‐veneris subsp. lanyuanum (Pteridaceae) in East Asia - Zhi‐Xiang Chang; Tian‐Chuan Hsu; Xinping Qi; Ching Ming Hsieh; Atsushi Ebihara; Yi‐Han Chang; Yao‐Moan Huang; Li‐Yaung Kuo (New Zealand Journal of Botany, 2026)
Adiantum capillus‐veneris is a species with a worldwide distribution, exhibiting considerable morphological variation, with several infraspecific names applied. Among these infraspecific taxa, A. capillus‐veneris subspecies lanyuanum can be easily distinguished from typical A. capillus‐veneris by its small and 1‐pinnate fronds. This form has been recorded from a few insular populations in Taiwan and Japan, typically inhabiting moist and shaded coral reef cliffs. A chloroplast DNA phylogeny further demonstrates that collections of subsp. lanyuanum across different populations formed a well‐supported clade, and also provides evidence of its genetic distinctiveness and differentiation. Further examination of herbarium specimens and field observations found that, in addition to frond morphology, the rhizome scale differences are also useful for distinguishing the two taxa. As a consequence, A. capillus‐veneris subsp. lanyuanum comb. nov. is proposed as the appropriate taxonomic designation of this taxa and a neotype is designated.

Selective Antimicrobial Activity of Slightly Acidic Electrolyzed Water: Differential Effects on Harmful and Beneficial Bacteria in Microbial Fermentation Systems - Shan Bing; Yao Zang; Haojie Zhu; Jiahong Han; Yingjie Feng; Wenduo Qiao; Chuan Li; Guosheng Zhang; Yanjiao Li; Nengshui Ding; Guoyun Wu; Yitian Zang (Environmental Microbiology, 2026)
Microbial contamination in fermentation systems poses significant risks to safety and efficiency, as harmful microbes can proliferate while conventional disinfectants often indiscriminately harm beneficial lactic acid bacteria (LAB). This study investigated the selective antimicrobial activity of slightly acidic electrolyzed water (SAEW) against Salmonella enteritidis ( S. enteritidis ) and Lactobacillus plantarum ( L. plantarum ) using monoculture, co‐culture and mechanistic analyses. Selectivity was dependent on available chlorine concentration (ACC): at 70 mg/L, S. enteritidis was completely eliminated, while > 40% of L. plantarum survived. In co‐culture, 57.7% of L. plantarum remained viable and recovered, whereas S. enteritidis showed no regrowth. Mechanistic analysis revealed that S. enteritidis was more susceptible due to its thinner cell walls and weaker antioxidant defenses, in contrast to L. plantarum 's thicker peptidoglycan layer and robust stress response, which provided partial resistance. To validate these findings in a practical fermentation context, SAEW was applied to Pennisetum sinese silage, where it suppressed undesirable microbes such as Enterobacter and Clostridium lachnoclostridium , enriched LAB populations and enhanced acidification. These results demonstrate SAEW as a residue‐free agent for targeted pathogen control and microbial community modulation in fermentation environments.

Integrated Workflow for Wellbore Stability in Horizontal Drilling of Unconsolidated Sandstone Reservoirs - Gang Li; Yanhui Han; Jianguo Zhang; Ziheng Yao; James Kalinec (Rock Mechanics and Rock Engineering, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Staphylococcus haemolyticus isolated from the Elaphurus davidianus: Pathogenicity and antimicrobial susceptibility profile - Yongcheng Meng; Qingyan Han; Mengling Han; Zhenpeng Li; Jie Wang; Sihan Zuo; Zhen Huang; Qian Mu; Yongli Hua; Wanling Yao; Wangdong Zhang (Research in Veterinary Science, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Partial root zone irrigation optimizes the trade-off between maize salt resistance and water saving in saline land - Yecheng Zhang; Xinzhu Li; Mengjiao Li; Zhongrui Li; Guangxu Yao; Shuhong Wang; Yanyan Cui; Huifang Han; Peng Liu; Kun Han (Field Crops Research, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Converting low-quality construction waste into tough pavement material via biomimetic mineralization - Long Wen; Zhi Zhao; Yang Li; Yiran Wang; Jiaran Han; Chuan Qiu; Hui Yao; Runhua Guo; Kai Li; Xiaoyan Song (Chemical Engineering Journal, 2026)

Spiral wrapped in-situ optic fiber tract - Hai Fu; Huifeng Yang; Xin Qiu; Zhi Chen; Yao Zhu; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2026)

Functional Breakdown of Temporoparietal Junction Interaction in High-depression Individuals: Evidence from Multi-Metric Connectomics - Xiaotong Wen; Yao Fengge; Bin Han; Guodong Wei; Yuehan Gao; Yuying Chen; Ziyu Hao; Huanhuan Li; Fengyu Dou (Brain Structure and Function, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

City-scale subsurface utilities mapping by multi-channel ground penetrating radar (MCGPR) with mobile mapping system (MMS) - Wallace Wai-Lok Lai; Phoebe Tin-Wai Wong; Rene Lee-Yee Kwan; Yaxin Li; Yimin Zhou; Wenchao He; Yao Han; Wu Chen (Tunnelling and Underground Space Technology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Corrigendum to “Based on the umami-transformer machine learning model: Screening of umami peptides from ultrasound-assisted enzymatic hydrolysis of shiitake mushrooms and study on their flavor mechanism” [Food Res. Int. 228 (2026) 118379] - Jingyi Han; Yao Li; Jiakang Liang; Lihong Chen; Xiaojie Yu; Li Chen; Otu Phyllis; Hafida Wahia; Hua Yang; Cunshan Zhou (Food Research International, 2026)

Ovalbumin amyloid fiber-based antibacterial edible film for Agaricus bisporus preservation - Miaomiao Han; Yuanyuan Shen; Shengjie Li; Yulong Wu; Chun Hua; Changqing Zhu; Ning Tang; Yao Cai; Chongjiang Cao; Feng Zhou (Food Chemistry, 2026)

Flow-induced shear enhancement of dynamic lubrication surfaces for combating complex biofouling in biliary stents - Jiaxin Liu; Junchang Guo; Wei Liu; Han Yao; Linjie Guo; Yuan Gao; Bingyang Lu; Luohuizi Li; Huali Yu; Jing Luo; Liansong Ye; Xu Deng; et al. (Chemical Engineering Journal, 2026)

Effects of short-term grazing prohibition on methane, nitrous oxide and nitric oxide fluxes from alpine meadows on eastern Tibetan Plateau - Xiao Chen; Rui Wang; Lei Ma; Han Zhang; Zhisheng Yao; Kai Wang; Wei Zhang; Siqi Li; Shenghui Han; Chunyan Liu; Yong Li; Xunhua Zheng (Agriculture, Ecosystems & Environment, 2026)

Effect of temperate phage SapYZUs891 as a biocontrol agent on the Chinese foodborne multidrug-resistant Staphylococcus aureus isolates - Xiaoxing Fan; Zhilan Yao; Yuhong Wu; Wenjuan Li; Yeling Han; Xuan Li; Aiping Deng; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Archives of Microbiology, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Immobilized Bacillus in polyvinyl alcohol-sodium alginate-biochar for petroleum-contaminated soil remediation - Fenglei Han; Zhoutong Liu; Lihan Ren; Biao Wang; Fan Yang; Feng Yao; Xiaodong Zhao; Xiuxia Zhang; Kang Xiong; De Li; Wenhao Zuo (Environmental Sustainability, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Singlet oxygen-driven degradation of organic pollutants via peroxymonosulfate activation by sulfur-doped MOF-derived catalysts - Huanxuan Li; Chen Liu; Tao Rao; Zhong Zhou; Zhitong Yao; Wei Han; Jingang Huang; Shaodan Xu; Xiuyan Liu (Process Safety and Environmental Protection, 2026)

Based on the umami-transformer machine learning model: Screening of umami peptides from ultrasound-assisted enzymatic hydrolysis of shiitake mushrooms and study on their flavor mechanism - Jingyi Han; Yao Li; Jiakang Liang; Lihong Chen; Xiaojie Yu; Li Chen; Otu Phyllis; Hafida Wahia; Hua Yang; Cunshan Zhou (Food Research International, 2026)

Bioactive polymethoxylated flavones from Clerodendranthus spicatus alleviate high-fat diet-induced lipid dysfunction and metabolic inflammation via targeting the PPARα/NF-κB pathway - Zheng Li; Yuqin Yao; Huayi Han; Qiongyue Cao; Binjie Tang; Yuhang Liu; Zhengkun Zhou; Wei Zhang (Food Research International, 2026)

Structural characterization, cryoprotective potential, and mechanistic insights of thawed drip proteolytic peptides - Xiaoyu Han; Jinxuan Cao; Shiqi Liu; Jinpeng Wang; Wendi Teng; Ming Li; Xianqi Yao; Bambang Kuswandi; Bayu Taruna Widjaja Putra; Ying Wang; Yuemei Zhang (Food Chemistry, 2026)

An oriented freezing strategy for fabricating fibrous structures of plant-based chicken analog - Yao Lin; Yu Peng; Li Shen; Qiuyu Han; Quanhong Li; Xiaojun Liao; Jing Zhao (Food Hydrocolloids, 2026)

Corrigendum to “MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting” [Chem. Eng. J. 525 (2025) 170080] - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2026)

Flash joule heating-induced synthesis of biowaste-derived metal-free catalysts for nitrate reduction reaction - Xin Chen; Zhaoyu Wang; Liuhong Yang; Runmiao Yuan; Shuyi Huang; Qinyuan Hu; Xue Wang; Cong Gu; Xiangli Wen; Xi Chen; Hongji Zhang; Dongjian Shi; et al. (Bioresource Technology, 2026)

Opportunity windows for scaling up soil nitrogen processes - Benyi Li; Mengfei Li; Yanzhong Yao; Bingbing Han; Shuli Niu; Zhaolei Li (Frontiers of Earth Science, 2026)

WT-A-LSTM-KAN: A novel hybrid deep learning framework for high-precision short-term prediction of moored ship roll and pitch motions - Jintong Li; Yanqing Han; Kangqiang Li; Qingtao Gong; Yao Teng; Shengtao Chu (Ocean Engineering, 2026)

Circ_0001839 modulates the oncogenic MYCL rs1038259890 (p.G83S) mutation to promote B[a]P-induced malignant transformation in 16HBE cells - Xintong Chen; Han Zhang; Shuwei Yao; Nan Zhang; Miaoyun Qiu; Saifeng Li; Senhuang Huang; Yangyang Jia; Wenfeng Lu; Chenghui Zhong; Yanni Yi; Yun Zhou; et al. (Journal of Hazardous Materials, 2026)

Synergistically enhanced foam dust suppressant based on Polyvinyl alcohol acetal crosslinking and hydrogen bond adsorption - Haiming Yu; Wang Li; Yao Xie; Han Qi; Jiayin Wang (Journal of Cleaner Production, 2026)

Synergistic degradation of polycyclic aromatic hydrocarbons by Fusarium and Priestia in saline environments: From kinetic characterization to multi-omics dissection - Fenglei Han; Zhoutong Liu; Xiuxia Zhang; Fan Yang; Biao Wang; Feng Yao; De Li; Kang Xiong; Lihan Ren (International Biodeterioration & Biodegradation, 2026)

Emergent constraints reveal underprediction of future global water availability under anthropogenic forcing - Senlin Tang; Qiang Zhang; Xintong Gong; Chong-Yu Xu; Vijay P. Singh; Fubao Sun; Yao Feng; Ziwei Li; Likun Han (Global and Planetary Change, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Dual improvement in thermal stability and flame retardancy of addition-cure liquid silicone rubber mediated by oxygen vacancy-rich fillers - Yue Xing; Yao Li; Hailan Kang; Feng Yang; Long Li; Wenchi Han; Genshi Liu; Qinghong Fang (Chemical Engineering Journal, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Shen-Ling-Bai-Zhu-San alleviates ulcerative colitis by enhancing mitophagy via the Nrf2/PINK1/Parkin pathway - Huan Wang; Jian Han; Lin Li; Yan Li; Jun Yang; Wangzhong Qiu; Liuhua Yao; Jianjun Zhou (Journal of Molecular Histology, 2026)

Amino-modified gangue-derived NaX zeolite for enhanced stabilization of lead and cadmium in contaminated soils: synthesis, performance, and leaching stability - Weiwei Zhu; Jingyi Xiong; Zhuoxi Huangfu; Jiang Yu; Pengxinyue Hang; Cheng Han; Ming Chen; Bin Li; Tao Gao; Junwei Yang; Yao Du (Environmental Geochemistry and Health, 2026)

Pan-Cancer Analysis of ANO6 and Experimental Validation in Metastatic Melanoma - Yao An; Haoran Dong; Meishan Yan; Caixu Liu; Danfeng Hu; Qi Liu; Jingqiu Zhang; Xu Han; Zimeng Li; Minghui Xu; Li Chen; Quanzhi Zhang; et al. (Biochemical Genetics, 2026)

Enhancement of microalgal carbon fixation via synergistic interactions with a facultative autotrophic bacterium Cytobacillus KQ-2 - Dandan Yao; Yunhui Li; Zhiqian Han; Ding Tan; Meng Wang; Huan Deng; Hui Wang; Yun Liu (Bioresource Technology, 2026)

Promoting Effect of (+)-Borneol on Alzheimer’s Disease Treatment in APP Transgenic Zebrafish and Its Blood-Brain Barrier Permeation Mechanism - Zhe Han; Hongsong Chen; Yuehua Yao; Xinru Bo; Xuan Ni; Haiping Liu; Meirong Bai; Tonglaga Li; Liming Bao; Dongwei Zhang; Wu Dong (Molecular Neurobiology, 2026)

Mendelian Randomization Unlocks Stroke Therapeutics: Dioscin Inhibits CD27-Driven Neuroinflammation via Gut Microbiota Modulation - Haozhou Tan; Shengli Li; Han Yan; Fangfang Li; Yang Yao; Ying Li; Qian Feng (Molecular Neurobiology, 2026)

Unraveling stress-mediated fluid-fault interactions in 2021–2022 seismic sequence: Insights from unsupervised machine learning and multiparametric hydrochemical anomalies in Xianshuihe fault zone - Yucong Yan; Zheming Shi; Xiaocheng Zhou; Guangcai Wang; Zuochen Zhang; Yunfei Bai; Zhaojun Zeng; Bingyu Yao; Yuwen Wang; Miao He; Jiao Tian; Ruibin Li; et al. (Applied Geochemistry, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Water migration and browning mechanisms in postharvest litchi pericarp: Insights from LF NMR - Yongqi Chen; Jingyi Li; Difa Zhu; Dongmei Han; Chulin Zhou; Yao Li; Yiwen Liu; Yuwei Ma; Tao Luo; Bingyi Wen; Zhenxian Wu (Postharvest Biology and Technology, 2025)

Template-free synthesis of nano/micro-polyarylamines and their enhanced selective precious metal ion Au(III) capture/reduction performance - Yao Li; Xingzhou Liu; Yiming Zhang; Weiming Gao; Zhilong Xu; Runxi Han; Dingwu Jiang; Hufei Dai; Hao Tian; Wen Li; Xiaotian Wei; Cuiping Li (Journal of Water Process Engineering, 2025)

Anthraquinone sites engineering of covalent organic frameworks enables efficient and selective 1O2 generation via directed oxidation of peroxymonosulfate - Yuzheng Wu; Jinyi Tan; Zifan Li; Luwen Liang; Bing Chen; Xinwen Ou; Shan Yao; Guiquan Che; Youqun Wang; Bin Han (Journal of Hazardous Materials, 2025)

Deep eutectic supramolecular polymerization networks modified acryloylated magnetic β-CD for efficient adsorption and removal of ofloxacin and tetracycline from water: Performance and mechanism - Jingyu Zhang; Yuhang Wang; Xiaoli Peng; Guangyi Xu; Liping Yao; Shanshan Bai; Shengnan Zhang; Zhihui Zhang; Yulin Han; Mingrong Qian; Zuguang Li (Journal of Environmental Chemical Engineering, 2025)

Quantifying nitrogen loss responses to seasonal deluges and droughts: A modeling study in a subtropical agro-forest catchment, upper Yangtze River - Wei Zhang; Xunhua Zheng; Siqi Li; Chunyan Liu; Zhisheng Yao; Shenghui Han; Rui Wang; Kai Wang; Bo Zhu; Minghua Zhou; Xiao Chen; Yong Li (Ecohydrology & Hydrobiology, 2025)

The flow and adhesion of Geldart Group C particles in the dipleg of cyclone separators - Li-Xin Yang; Jian-Yi Chen; Han-Gong Zhang; Bo Hu; Kang-Shuai Liu; Jian-Jun Zhu; Yao-Dong Wei (Chemical Engineering Journal, 2025)

Dynamic 3-hydroxyflavone-modified D-alanine nanoparticles for metabolic-incorporation in anaerobic, pathogenic biofilms generating CO in infected periodontal pockets - Da-Yuan Wang; Jing Li; Xiao-Han Tian; Siyu Zhang; Yao Chen; Feihe Ma; Henk.J. Busscher; Jing Shen; Linqi Shi (Chemical Engineering Journal, 2025)

MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2025)

Improved nitrogen removal from real mariculture effluent by halotolerant bacterial consortium SND223: Preparation, entrapping application, and mechanism - Xin Su; Shihan Wang; Xiaoqian Cheng; Jing Song; Qing Li; Guixi Yao; Rui Han; Yinghai Wu (Bioresource Technology, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Uncovering the gut microbiome and antibiotic resistome of mammals on the Tibetan Plateau - Chen Tian; Zecheng Tang; Xiaoyu Zhang; Xueqin Yao; Yitian Li; Daohua Zhuang; Yu Luo; Teng Li; Liyan Bai; Fangfang Zhao; Lei Zhu; Guolin Shi; et al. (Science China Life Sciences, 2025)

FOXO1 contributes to cigarette smoke condensate–induced cellular senescence and fibrosis in lung fibroblasts through activating the TGF-β1/Smad2/3 signaling pathway - Mengning Zheng; Guohang Yuan; Jing Han; Jiayi Li; Youjun Jiang; Zhaoxia Li; Yang Yao (Immunologic Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Divergent drought-induced suppression on vegetation and associated feedbacks: Satellite-based observations in 2022 across the Yangtze River basin, China - Lei Han; Yanan Chen; Chaoyang Wu; Li Yao; Ying Wang; Chao Su; Xuan Li; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Xuguang Tang (Journal of Hydrology, 2025)

Achieving partial nitritation-anammox in membrane-aerated biofilm reactor by hydroxylamine addition - Ning Mei; Fangxu Jia; Ying Liu; Yiran Li; Xin Qi; Baohong Han; Xu Zhang; Tao Liu; Hong Yao (Journal of Environmental Management, 2025)

Unveiling temperature-dependent dual effects of HCHO on NH3-SCR: Mechanistic insights into HCN suppression over the Mn-Co catalysts - Li Han; Zihao Hu; Baoyi Wang; Chen Wang; Jiali Zhu; Jing Li; Wei Wang; Shuiliang Yao; Nan Xu; Erhao Gao; Zuliang Wu (Fuel, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

Efficient tanshinone metabolic engineering in Salvia miltiorrhiza through modified multiplex CRISPR/Cas9 system - Han Zheng; Qi Yao; Qi Liu; Badalahu Tai; Yi Ye; Ling Li; Yaojie Zhang; Yuyang Zhao; Xiaokai Gao; Shuai Liu; Xueqing Fu; Muyao Yu; et al. (Chemical Engineering Journal, 2025)

Regulating charge separation by structure adjusting in pyrene-based 1D COFs for efficient photocatalytic hydrogen evolution - Bing Han; Shuyan Wang; Xianglin Yu; Xuxin Fan; En Liang; Yao Yang; Huan Zhang; Changyu Qin; Junbo Li (Chemical Engineering Journal, 2025)

One-step dual-functional modification of Ni-rich cathodes via DFT prediction for high-rate quasi-solid-state batteries - Yunting Wang; Gaohui Du; Di Han; Weihao Shi; Liming Wang; Libing Yao; Huayu Li; Jingyi Jing; Shaochen Wei; Shixian Chen; Wenqi Zhao; Qingmei Su (Chemical Engineering Journal, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Exploring the impact of follicular fluid exosomes on porcine cumulus cell and oocyte function: Regulatory network analysis based on the ENSSSCG00000042788/ssc-miR-504/PDHA1 axis - Junzheng Zhang; Shuang Ji; Yue Han; Yuyang Zhang; Hao Li; Shunfa Yao; Qinglong Xu; Kun Zhao; Jie Wang; Zhiwei Yao; Yang An; Yi Jin (Theriogenology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Sb-doped Cu-Fe/TiO2 catalysts with enhanced K-poisoning resistance for simultaneous NO and CO removal - Yang-wen Wu; Zheng-long Wu; Hai-yuan Zhao; Han-wen Wang; Yao Dong; Xin-yue Zhou; Jing-tao Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Substrate chemistry trumps mineral protection in governing temperature sensitivity of organic carbon mineralization in saline lake sediments - Beichen Wang; Xiaoxi Sun; Zhen Yang; Xinyi Li; Bingfu Yao; Min Cai; Tianran Sun; Jian Yang; Jibin Han; Xiying Zhang; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Non-pre-irradiation multicolor mechanoluminescence in piezoelectric Ca3Ga4O9 for secure channel encryption - Ying Zhang; Hengxi Yao; Jiawen Fan; Jia Li; Tianyi Wang; Canlin Zhou; Jiawei Yan; Tong Wei; Linyang Li; Dengfeng Peng; Yingdong Han (Chemical Engineering Journal, 2025)

Targeting the mitochondrial-autophagy axis in pituitary neuroendocrine tumors via intracellular copper overload - Yao Feng; Han Wang; Hanyang Zhou; Ni Li; Yanting Liu; Yang Lu; Zhe Bao Wu; Dalong Ni; Li Xue (Chemical Engineering Journal, 2025)

Ultrasound-triggered piezocatalytic MOF(Hf)-Pt nanozymes for efficient ROS scavenging in the treatment of osteoarthritis - Yi Yao; Zixin Gao; Zhongjie Pan; Yanping Zhong; Lili Qin; Kexin Zhao; Shuhan Liu; Shengqing Zhang; Haoyang Han; Feiying Yin; Ruizheng Liang; Jinmin Zhao; et al. (Chemical Engineering Journal, 2025)

Insights into the catalytic effects of Fe2O3 on PEN plastic waste degradation in supercritical water - Houjun Zhang; Bingyan Sun; Xiangyu Li; Hongyang Tian; Yao Nian; Jinli Zhang; You Han (Chemical Engineering Journal, 2025)

Chemotaxonomic significance of chemical constituents from Ligia exotica, sea slater - Yue-Yao Li; Fei-Hua Yao; Qian Han; Jin-Li Luo; Xin-Yue Li; Cheng-Hai Gao; Xiang-Xi Yi (Biochemical Systematics and Ecology, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Phosphorus-modified cobalt-carbon hybrid catalysts derived from MOFs for enhanced peroxymonosulfate activation: Mechanistic insights and toxicity assessment - Chen Liu; Huanxuan Li; Tao Rao; Zhong Zhou; Zhitong Yao; Wei Han; Xiuyan Liu; Jingang Huang; Haoqi Wang; Shaodan Xu (Process Safety and Environmental Protection, 2025)

Fe-C micro-electrolysis supercharged EGSB: Breaking toxicity barriers in waste acid condensate treatment for maximum COD/NH3-N and H2S control - Yanhe Han; Xueao Li; Hao Yao; Fan Zhao; Naif Abdullah Al-Dhabi; Qingpeng Zhao; Mengxiang Wei; Zhi Guo; Hua Ji; Lei Zhang; Wangwang Tang; Xuejiao Ma (Journal of Water Process Engineering, 2025)

A double-antibody sandwich ELISA for sensitive and specific detection of insulin-like growth factor 1 in goat milk - Yaxian Shang; Yinting Hao; Jing Liu; Jingyu Gong; Yao Wang; Mengdi Han; Dekun Chen; Jia Li (Food Bioscience, 2025)

Nitrogen-removal improvement and the mechanisms using a composite carbon source synthesized by alkali-modified cherrywood and polyhydroxybutyrate-co-valerate in an aerated solid-phase biofilter treating saline and low C/N ratio wastewater - Guixi Yao; Xiaoqian Cheng; Qing Li; Peng Zhou; Peiwu Liu; Rui Han; Yinghai Wu (Chemical Engineering Journal, 2025)

Dual-phased nickel sulfide heterojunction of Ni9S8/Ni3S2 doped with Co assembled on Ni foam as a highly efficient electrocatalyst for alkaline oxygen evolution reaction - Siqi Zhang; Chaonan Wang; Wenyi Peng; Jiahao Huang; Senkai Han; Siao Li; Rong Liu; Shulan Ma; Huiqin Yao (Chemical Engineering Journal, 2025)

Formation of early continental crust by remelting of hydrothermally altered oceanic crust: Evidence from potassium and oxygen isotopes - Shao-Bing Zhang; Liang Zhang; Xing-Yu Yao; Zhen-Xin Li; Xiaoqiang Li; Guilin Han; Yong-Fei Zheng (Chemical Geology, 2025)

Study on Joint Flood Control and Peak Shaving Optimization Operation of Reservoir Groups Based on Flood Operation Phase Division - Min Li; Xiaoye Han; Yonggao Yao; Wei Ding; Qianning Wang; Jianhua Luo; Feilin Zhu (Water Resources Management, 2025)

A Comparative Analysis of Subtyping Methodologies on Cross-sectional sMRI Data - Shirui Zhang; Baitong Zhang; Kun Zhao; Zhuangzhuang Li; Pan Wang; Dawei Wang; Chengyuan Song; Jie Lu; Zengqiang Zhang; Hongxiang Yao; Tong Han; Chunshui Yu; et al. (Neuroscience Bulletin, 2025)

Self-assembly of multi-arm star PEG containing TXA9 into nanoparticle for the efficient chemotherapy of NSCLC - Qilong Wang; Zhe Liu; Jiale Yao; Haosheng Xie; Zhihui Liu; Jianxiu Zhai; Sikai Li; Jia Ming Zhang; Na Han; Jun Yin (Drug Delivery and Translational Research, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Fish Swimming Behavior and Strategies Under Different Hydrodynamic Conditions in Fishways with Various Vertical Slot Configurations - Lijian Ouyang; Dongqiu Li; Shihao Cui; Xinyang Wu; Yang Liu; Xiaowei Han; Shengzhi Zhou; Gang Xu; Xinggang Tu; Kang Chen; Carlo Gualtieri; Weiwei Yao (Fishes, 2025)
Vertical slot fishways are a crucial measure to mitigate the blockage of fish migration caused by hydraulic engineering infrastructures, but their passage efficiency is often hindered by the complex interactions between fish behavior and hydrodynamic conditions. This study combines computational fluid dynamics (CFD) simulations with behavioral laboratory experiments to identify the hydrodynamic characteristics and swimming strategies of three types of fishways—Central Orifice Vertical Slot (COVS), Standard Vertical Slot (SVS), and L-shaped Vertical Slot (LVS)—using the endangered species Schizothorax prenanti from the upper Yangtze River as the study subject. The results revealed that (1) a symmetric and stable flow field was formed in the COVS structure, yet the passage ratio was the lowest (50%); in the SVS structure, high turbulent kinetic energy (peak of 0.03 m2/s2) was generated, leading to a significant increase in the fish’s tail-beat angle and amplitude (p 0.68). The LVS structure achieved the highest passage ratio and shortest transit time for Schizothorax prenanti, demonstrating its superior functionality for upstream migration. This design balances hydrodynamic complexity with low-turbulence refuge zones, providing a practical solution for eco-friendly fishways.

Wear performance of steel plough tips on high-speed hydraulic turning ploughs - Qiang Yao; Xiaorui Han; Mingjian Li; Zhanhong Guo; Pengwei Fan; Youqiang Zhang (Biosystems Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Phosphate-solubilizing bacteria reduce Cd accumulation in spinach by forming P–Ca adhesive films in the roots and altering the structure of soil macroaggregates - Qingzhao Zhao; Jiexun Wang; Haoyuan Li; Ziyi Wang; Randa S. Makar; Lunguang Yao; Zhaojin Chen; Hui Han (Journal of Hazardous Materials, 2025)

Self-assembly of Zein-based nanoparticles for oral isoliquiritigenin delivery against Salmonella infections - Cang Li; Yu Huang; Yuchen Liu; Zhipeng Li; Yao Deng; Hao Ren; Donghao Zhao; Lu Han; Jian Sun (Innovative Food Science & Emerging Technologies, 2025)

Modelling forest-atmosphere exchanges of carbon and water using an improved hydro-biogeochemical model in subtropical and temperate monsoon climates - Wei Zhang; Xunhua Zheng; Siqi Li; Shenghui Han; Chunyan Liu; Zhisheng Yao; Rui Wang; Kai Wang; Xiao Chen; Guirui Yu; Zhi Chen; Jiabing Wu; et al. (Ecological Modelling, 2025)

Genotyping by target sequencing (GBTS)-based genetic mapping uncovers synergistic interactions for stripe rust resistance in wheat cultivar Flanders - Lei Liu; Jinyu Han; Dandan Zhang; Yuqing Li; Chuanliang Zhang; Shengjie Liu; Ziyi Yan; Weijun Zheng; Chunlian Li; Qingdong Zeng; Zhensheng Kang; Dejun Han; et al. (Theoretical and Applied Genetics, 2025)

Single-Cell RNA Sequencing Delineates the Atlas and Cell Interactions of the Testicular Cells in Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Jingting Yao; Sendong Li; Wenzhuo Ban; Linhui Zeng; Han Cui; Kaili Chen; Hongyan Xu (Marine Biotechnology, 2025)

Topological surface states in γ-PtBi2 evidenced by scanning tunneling microscopy - Yunkai Guo; Jingming Yan; Wen-Han Dong; Yongkai Li; Yucong Peng; Xuetao Di; Caizhen Li; Zhiwei Wang; Yong Xu; Peizhe Tang; Yugui Yao; Wenhui Duan; et al. (Science Bulletin, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Brain structural reorganization mediates the relationship between hearing loss and cognitive impairment - Yao Wang; Jianfen Luo; Wenqing Li; Yu Han; Wen Ma; Siqi Liu; Lei Xu; Zhaomin Fan; Yu Ai; Meixia Su; Fuxin Ren; Fuyan Li; et al. (Brain Imaging and Behavior, 2025)

Balancing textile waste recovery technologies from the environmental, economic, and technological perspectives - Peifan Yao; Fuzheng Shan; Dingyi Li; Han Wang; Lijie Song; Jun Tai; Zhuo Zhang; Qi Tian; Jiefeng Xiao; Zhujie Bi; Jun Zhao; Guangren Qian (Sustainable Production and Consumption, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Undescribed alkaloids, peptides and polyketides from marine sediment-derived fungus Aspergillus terreus PPS1 - Yao-Yao Zheng; Guang-Shan Yao; Jiao-Jiao Li; Na Han; Jun-Qiu Mao; Ya-Hui Zhang; Ling Lv; Yang Liu; Chang-Yun Wang (Phytochemistry, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Hydroxyapatite combined with phosphate-solubilizing bacteria immobilized of Cd and inhibited the absorption of Cd by lettuce - Ke Wang; Junqing Zhang; Weilin Li; Zhongyan Deng; Randa S. Makar; Lunguang Yao; Hui Han (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

RcPLATZ8 as a novel negative regulator of flowering in Rosa chinensis - Yifang Peng; Qi Li; Yao Gong; Qian Yang; Qijing Dong; Yu Han (Plant Cell Reports, 2025)

Protein Kinase C Epsilon Overexpression Protects the Heart Against Doxorubicin-Induced Cardiotoxicity Via Activating SIRT1 - Danyong Liu; Chunyan Wang; Yao Chen; Xiaolei Huang; Yajie Wen; Shan Duan; Yin Cai; Xia Li; Jianfeng He; Kaijia Han; Ting Li; Yuantao Li; et al. (Cardiovascular Toxicology, 2025)
Doxorubicin (DOX)-induced cardiotoxicity (DIC) is known to be associated with reduction of cardiac protein kinase C epsilon (PKC-ε). PKC-ε promotes cell survival and protects hearts against various stresses. However, it is unclear whether or not the reduction in cardiac PKC-ε expression plays a causal role in DIC and in particular the potential underlying mechanism whereby PKC-ε may protect against DIC. C57BL/6 mice (8–10-week-old) were either treated with DOX administered intraperitoneally for a duration of 4 weeks to produce cardiotoxicity, or untreated in which mice received the same volume of saline. In vitro, neonatal rat ventricle cardiomyocytes were exposed to DOX for 24 h in the absence or presence of adenovirus overexpressing PKC-ε. Cardiomyocytes in a subgroup were treated with sirtuin-1 (SIRT1) selective inhibitor Ex527. Four weeks after DOX, cardiac contractile function was decreased concomitant with increased serum CK-MB and LDH levels as well as increases in Bax-to-Bcl-2 ratio and Cleaved Caspase 3 proteins expression, while PKC-ε and Sirt1 protein expressions were significantly decreased. In vitro, DOX reduced cardiomyocyte PKC-ε and SIRT1 protein expression, decreased cardiomyocyte viability, and increased LDH release with concomitant increases in oxidative stress and apoptosis. These changes were attenuated by overexpression of PKC-ε. IP study showed that PKC-ε could directly or indirectly bind SIRT1 in cardiomyocytes, and the protect effects of PKC-ε were further canceled by SIRT1 inhibition. In conclusion, activating SIRT1 may represent a major mechanism whereby PKC-ε protects the heart against DOX-induced cell apoptosis and oxidative stress. Graphical Abstract Dox induces cardiotoxicity via inhibiting PKC-epsilon/Sirt1 signaling which can be reversed by PKC-epsilon overexpression.

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Sublethal and transgenerational effects of nitenpyram on Acyrthosiphon gossypii and its impacts on symbiotic bacteria - Yindi Wei; Wenjie Li; Ting Chen; Yue Su; Xu Han; Yongsheng Yao (Crop Protection, 2025)

Amorphous-microcrystalline heterostructured high-entropy oxysulfide/cerium oxide with strong electronic communication to boost water/simulated seawater splitting - Han-Ming Zhang; Jiakang Li; Min Yao; Yali Li; Jinfeng Sun (Science of The Total Environment, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Organic acid promoting the degradation of nonylphenol by persistent free radicals in biochar - Jie Ji; He Zhang; Feichao Zhang; Yao Wu; Han Zhang; Ziwei Mei; Wenxuan Zhou; Liang Li; Hong Tao; Meicheng Wen (Chemical Engineering Journal, 2025)

Hierarchical assembly of NiMoO4/Mo3Se4/Ni3Se2 in situ grown on nickel foam as a highly efficient and durable electrocatalyst for alkaline hydrogen evolution reaction - Senkai Han; Chaonan Wang; Yicheng Zhang; Wu Li; Siqi Zhang; Shaoshi Guo; Shulan Ma; Huiqin Yao (Chemical Engineering Journal, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Distribution and relationship of heavy metals, microbial communities and antibiotic resistance genes in the riparian soils of Daye Lake, China - Liting Yang; Jing Li; Bingyao Liu; Han Xu; Xuanzi Guo; Jing Wang; Yao Zhang (Environmental Geochemistry and Health, 2025)

The assembly of a Malus sieversii regulatory network reveals gene resistance against Alternaria alternata f. sp. mali when colonized by Trichoderma biofertilizer - Shida Ji; Dechen Li; Jin Yao; Bin Liu; Jing Han; Yucheng Wang; Zhihua Liu (Journal of Plant Research, 2025)

Contrasting roles of abundant and rare root-associated fungi in wheat: Community assembly, heritability and agronomic impacts - Xia Kang; Yuyin Zheng; Zhihan Feng; Minjie Yao; Xiangzhen Li; Dejun Han; Qingdong Zeng; Hao Tan; Yumin Yang; Jiabao Li (Applied Soil Ecology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Improving real-time flood forecasting updating through a complete and non-excessive precipitation adjustment - Shuhong Xu; Qiongfang Li; Xiaoqiang Yang; Junliang Jin; Xingye Han; Zhengmo Zhou; Yao Du; Yiqun Sun; Wei Si; Peng Shi (Journal of Hydrology, 2025)

A novel dual-responsive NIR fluorescent probe based on isophorone: Real-time detection of Al3 + in vivo and colorimetric sensing of pH through smartphone - Ya-Tong Liu; Yue Hou; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Meng-Xun Zhang; Hao Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2025)

Effect of lactic acid on short-chain fatty acids and hydrogen production during anaerobic fermentation of acidified food waste - Xudong Wang; Xujia Ming; Xiao Han; Yao Liu; Mengyu Chen; Ting Zhang; Xianguo Li; Dahai Zhang (Fuel, 2025)

Characterization of flavor profiles of wines produced with Coniella vitis-infected grapes by GC–MS, HPLC, and sensory analysis - Xing Han; Yanfeng Wei; Lifang Yuan; Xiangtian Yin; Yao Liu; Chundong Wang; Xilong Jiang; Tinggang Li; Qibao Liu (Food Chemistry, 2025)

Uncovering soil heavy metal pollution hotspots and influencing mechanisms through machine learning and spatial analysis - Xiaoyong Song; Yao Sun; Huijuan Wang; Xinmiao Huang; Zilin Han; Yilan Shu; Jiaheng Wu; Zhenglin Zhang; Qicheng Zhong; Rongxi Li; Zhengqiu Fan (Environmental Pollution, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

One-pot synthesis of hierarchical assembly of NiMoO4/MoS2/Ni3S2 on nickel foam for highly efficient and durable electrocatalytic hydrogen evolution reaction in a wide pH range - Senkai Han; Huiqin Yao; Jiayi Zhan; Chaonan Wang; Siqi Zhang; Qingyang Gu; Cheng Li; Shenghan Zhang; Hongliang Dong; Shulan Ma (Chemical Engineering Journal, 2025)

Cross-Response of Sugar Beet to Different Salt Concentrations Under Drought Stress - Yaru Zhang; Qiqi Cai; Xiaodong Li; Pingan Han; Vadim N. Nurminsky; Jing Shi; Gui Geng; Jiahui Liu; Yao Xu; Yuguang wang (Sugar Tech, 2025)

Nature–based nutrient management through returning agricultural organic waste enhances soil aggregate organic carbon stability - Yini Wang; Yanzhong Yao; Bingbing Han; Simon Willcock; Jonathan Storkey; Xunzhuo Dong; Yunyao Zhong; Xiaozhong Wang; Yan Deng; Wei Zhang; Qirui Li; Xinping Chen; et al. (Agriculture, Ecosystems & Environment, 2025)

A New Screening Strategy for Flavonoid Components to Obtain a Satisfactory Co-Amorphous System with Piperine - Jiawei Han; Wen Sun; Yongxu Yao; Shuo Li; Zhimin Yue; Weitao Fang; Xiaoqian Liu; Jue Wang; Jiaxin Chen (AAPS PharmSciTech, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Study on the morphodynamic response of reef flat with moveable bed to monochromatic waves - Yu Yao; Zhangyan Li; Zhongwei Zhao; Long Chen; Baobao Zhou; Xiuqi Han (Marine Geology, 2025)

A near-infrared multifunctional fluorescent bio-probe with large stokes shift and high quantum yield for effective determination of heavy metal lead and pesticide glyphosate in vitro and vivo - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Hua-Yong Zhao; Jing-Yi Li; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

Efficiently selective inactivation of Gram-positive bacteria by MCM-41 molecular sieve-supported copper-based self-cascading nanozymes - Xue-Yao Pang; Fan-Xiang Meng; Cheng Ma; Si-Yang Ni; Zi-Han Jia; Bo Li; Yu-Xiang Liu; Wei-Wei Gao (Chemical Engineering Journal, 2025)

Injectable melatonin carbon dot composite hydrogel enhances anti-inflammatory and tenogenic differentiation of tendon-derived stem cells for minimally invasive treatment of Achilles tendinopathy - Zheyu Yao; Zheyang Yuan; Qianglong Chen; Liwei Yao; Xiqian Zhang; Xiang Gao; Senyi Wu; Yiding Shao; Jiahui Feng; Xufeng Mao; Wenmiao Shu; Junxi Wu; et al. (Chemical Engineering Journal, 2025)

Interplay between aridity changes and urban expansion across Chinese cities - Congrui Yi; Xia Li; Yuanzhi Yao; Xiaocong Xu; Han Zhang; Yuxia Wang (Applied Geography, 2025)

Spatiotemporal distribution and mechanism of Mesozoic magmatism in the Taiwan Strait and its adjacent areas: insights from seismic, geochemical, and geochronological data - Song Zhu; Yanfei Han; Zhe Wang; Shengzhong Ma; Kai Liang; Li Zhang; Yongjian Yao; Jianglang Tang; Ziying Xu; Chupeng Yang; Shantang Yi; Wenbo Du (International Geology Review, 2025)

Biofilm-state probiotics: Advanced alternatives to traditional probiotics - Boqing Yao; Zeqian Yang; Xiaorui Zhao; Zixin Han; Pinglan Li; Nan Shang (Trends in Food Science & Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An Intermittent Fasting Intervention for Black Adults Can Be Feasibly Implemented in Black Churches: A Cluster Randomized Controlled Pilot Study - Karen H. Kim Yeary; Detric Johnson; Narseary Harris; Han Yu; Frances G. Saad-Harfouche; Cassy Dauphin; Elizabeth DiCarlo; Tessa Flores; Song Yao; Krista Varady; Li Tang (Journal of the Academy of Nutrition and Dietetics, 2025)

In situ construction of FeCo nanoparticles decorated nitrogen-doped carbon nanofibers with surface-grown carbon nanotubes as lightweight and high-efficiency microwave absorbers with good environmental tolerance - Siyi Tong; Yao Li; Xiang Ding; Ruqu Han; Kaiyin Zhang; Jun Xiang (Journal of Environmental Chemical Engineering, 2025)

Experimental study on the performance of a novel data center air conditioner combining air cooling and evaporative cooling - Yaxi Zhang; Haixiao Han; Yanqiu Zhang; Jun Li; Yao zheng; Changxiong Liu; Yubo Liu; Diance Gao (International Journal of Refrigeration, 2025)

Insights into the potential quality markers of Rubus chingii Hu fruit at different growth stages - Ruiwen Yang; Bing Han; Biao Wang; Jun Qian; Yao Wang; Liqin Li; Guoyin Kai (Food Research International, 2025)

Antibacterial mechanism of atmospheric cold plasma against Pseudomonas fluorescens and Pseudomonas putida and its preservation application on in-packaged red shrimp paste - Jiajie Hu; Yao Zhang; Weicong Pan; Qianyun Han; Yu Wei; Yuwei Li; Yi Hu; Xiaoguo Ying; Andrea Armani; Alessandra Guidi; Shanggui Deng (Food Chemistry, 2025)

All-solid-state wire-shaped micro-supercapacitors: A microfluidic approach to core-shell structured bacterial cellulose-GN/PPy fibers - Yue Jiao; Yao Wang; Huining Xiao; Jian Li; Changtong Mei; Qiliang Fu; Jingquan Han (Carbohydrate Polymers, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Compatibility of Calycosin-Tanshinone IIA improves Ang II-induced renal artery endothelial cell dysfunction through lncRNA-mRNA co-expression network - YanYun Jiang; Cong Han; WanLi Xu; YuQiu Li; Yao Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Reconstructing Tarim within Rodinia: Constraints from early Tonian accretionary and collisional records in the Altyn belt - Wei Li; Jinlong Yao; Guochun Zhao; Yigui Han; Qian Liu; Donghai Zhang (Precambrian Research, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Soil aggregate carbon accrual via the microbial life footprint with nutrient management in worldwide croplands - Yini Wang; Yanzhong Yao; Bingbing Han; Yunyao Zhong; Xunzhuo Dong; Xiaozhong Wang; Lihua Ma; Xinping Chen; Zhaolei Li (Journal of Cleaner Production, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Application of carbon quantum dots as fluorescent probes in the detection of antibiotics and heavy metals - Fang Wang; Yuchen Zhang; Hui Li; Wenwen Gong; Jiajun Han; Shanxue Jiang; Dandan Li; Zhiliang Yao (Food Chemistry, 2025)

A ratiometric fluorescent probe for the determination of quinolone antibiotics in milk based on N and S co-doped carbon quantum dots - Fang Wang; Xiaoyun Li; Yuchen Zhang; Hui Li; Shanxue Jiang; Jiajun Han; Wenwen Gong; Dandan Li; Zhiliang Yao (Food Control, 2025)

Zein film loaded with Fructus Ligustri Lucidi essential oil: Preparation, characterization and application in fresh-cut apple preservation - Hong Chen; Chengyan Yang; Xiangxun Zhuansun; Yao Li; Rui Han; Longgang Wang; Shengqing Ding; Qi Liu (Food Control, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

The role of data resolution in analyzing urban form and PM2.5 concentration - Ziwei Zhang; Han Zhang; Xing Meng; Yuxia Wang; Yuanzhi Yao; Xia Li (Computers, Environment and Urban Systems, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Genome-wide elucidation and expression features of Q-type C2H2 zinc finger protein gene family in Rhododendron henanense subsp. lingbaoense - Yonghui Li; Huiping Ma; Siyu Chen; Yao Chen; Xiaojun Zhou; Xiangli Yu; Yafang Zhang; Junwang Han; Hailiang Wang (Genetic Resources and Crop Evolution, 2025)

Multi objective motion planning of fruit harvesting manipulator based on improved BIT* algorithm - Peifeng Ma; Aibin Zhu; Yihao Chen; Yao Tu; Han Mao; Jiyuan Song; Xin Wang; Sheng Su; Dangchao Li; Xia Dong (Computers and Electronics in Agriculture, 2024)

Design and green synthesis of asymmetric 3,4,5-trimethoxyphenyl-inspired 1,5-diaryl-1,4-pentadien-3-ones as potent anti-gastric cancer agents through ROS and JNK-triggered apoptosis - Jianzhang Wu; Song Yao; Danjie Wang; Mengke Han; Yingwen Liu; Shuo Ren; Liping Chen; Min Zhu; Qian Li; Tao Wu; Yujia Li; Jiabing Wang; et al. (Sustainable Chemistry and Pharmacy, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Dual-directional regulation of extracellular respiration in Shewanella oneidensis for intelligently treating multi-nuclide contamination - Xin-Lu Cai; Xuan Yao; Li Zhang; Yu-Han Chai; Xuan Liu; Wen-Wen Liu; Ruo-Xi Zhang; Yang-Yang Fan; Xiang Xiao (Journal of Hazardous Materials, 2024)

Facile synthesis of geopolymer-based hierarchical porous materials for efficient adsorption-photocatalysis of dye wastewater - Han Xiao Su; Chan Juan Li; Yao Jun Zhang (Journal of Environmental Chemical Engineering, 2024)

Vacuum freeze drying combined with catalytic infrared drying to improve the aroma quality of chives: Potential mechanisms of their formation - Jingyi Han; Jiakang Liang; Yao Li; Hafida Wahia; Otu Phyllis; Cunshan Zhou; Lei Zhang; Li Chen; Xuguang Qiao; Haile Ma (Food Chemistry, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Partitioned granular sludge coupling with membrane-aerated biofilm reactor for efficient autotrophic nitrogen removal - Ning Mei; Fangxu Jia; Hui Wang; Zhifeng Hu; Baohong Han; Yao Chen; Xingcheng Zhao; Xiangyu Han; Jingjing Zhang; Dongmei Li; Hong Yao; Jianhua Guo (Bioresource Technology, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Effects of temperature and particle size on the filter-feeding rate of brine shrimp Artemia franciscana at different growth stages and stocking densities - Ke Li; Yudie Wang; Guoru Du; Xueliang Yao; Haiyan Bao; Xuekai Han; Liying Sui (Aquaculture International, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Neurotoxicity induced by aged microplastics from plastic bowls: Abnormal neurotransmission in Caenorhabditis elegans - Liangzhong Li; Ruixue Ma; Yuan Yuan; Qian Yao; Yajing Han; Hanlin Cao; Jianying Qi (Science of The Total Environment, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Multifunctional ANF/ CNT/FCIP aerogels with superior sound and electromagnetic wave absorption and mechanical properties - Qing Ma; Junru Yao; Cheng Shen; Jintang Zhou; Pengfei Wang; Li Cheng; Jinling Gao; Tianjian Lu; Han Meng (Chemical Engineering Journal, 2024)

Polymerized lignin based carbon nanofiber for high-performance energy generator and storage - Chuangqi Zheng; Qiping Cao; Lei Pu; Jingyu Xu; Hui Gong; Ziyi Shen; Kaibin Chu; Dechao Chen; Qin Li; Ning Han; Yao Li (Chemical Engineering Journal, 2024)

Catalytic hydrolysis of HCN on the coupled sites of Lewis acid and surface hydroxyl of Fe-BEA catalyst leading to the presence of HCHO positively affects NH3-SCR activity - Li Han; Wenjing Feng; Qi Jin; Jiacheng Xu; Zuliang Wu; Jing Li; Jiali Zhu; Wei Wang; Erhao Gao; Shuiliang Yao; Nan Xu; Daiqi Ye (Chemical Engineering Journal, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

A Ratiometric Fluorescence Biosensor for Detection of Alkaline Phosphatase Via an Advanced Chemometric Model - Yao Chen; Jing-Jing Han; Bo-Wen Li; Li-Bo Nie; Ying Tang; Tong Wang (Journal of Fluorescence, 2024)

Effects of coexisting nanomaterials on the photodegradation behavior and ecotoxicity of antibiotics in the aqueous - Yang Yang; Yao Tong; Qi Han; Li Feng; Peng Gao; Liqiu Zhang (Chemosphere, 2024)

Sediment porewaters serve as a transient organic carbon pool at the land-ocean interface - Kang Li; Bin Zhao; Lulu Han; Tiantian Ge; Nan Wang; Peng Yao (Water Research, 2024)

Comparison of drug-induced liver injury risk between propylthiouracil and methimazole: A quantitative systems toxicology approach - Qingfeng He; Min Li; Peiying Ji; Aole Zheng; Li Yao; Xiao Zhu; Jae-Gook Shin; Volker M. Lauschke; Bing Han; Xiaoqiang Xiang (Toxicology and Applied Pharmacology, 2024)

Spatial heterogeneity, sediment-water exchange, and diffusion mechanisms of organophosphate esters from river to coastal aquatic system in a typical economic circle of northern China - Chengfeng Wang; Xindong Ma; Ziwei Yao; Dongfei Han; Guoliang Dai; Minghao Li; Yanjie Qi (Science of The Total Environment, 2024)

Destabilization mechanisms of Semi-aerobic aged refuse biofilters under harsh treatment conditions: Evidence from fluorescence and microbial characteristics - Yuansi Hu; Yuanyuan Feng; Li Yao; Chuanwei Wu; Mengli Chen; Han Zhang; Qibin Li (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction of bienzyme-inorganic hybrid nanoflowers as a high-efficiency biocatalyst for the degradation of indole - Jiping Han; Qiang Zhang; Ke Zhang; Ying Liu; Deyu Rao; Yaohua Gu; Mingming Li; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Harnessing donor cyclization strategy: Converting type II to type I photosensitizers and enhancing AIE performance for NIR-II FL/MR imaging-guided photodynamic therapy under hypoxia condition - Chonglu Li; Jie Li; Yida Pang; Longcan Mei; Wenhan Xu; Zhipeng Zhang; Cuipin Han; Yao Sun (Chemical Engineering Journal, 2024)

Mechanically customizable lignin bio-elastomers based on tailorable multiscale microstructures - Dengfeng Wang; Mengyuan Diao; Yaotao Shan; Han Wu; Lin Liu; Zihan Li; Haojie Hong; Juming Yao (Chemical Engineering Journal, 2024)

Contribution of gut microbiota to biodegradation of polystyrene in Tenebrio molitor larvae: Microbiome under antibiotic suppression of Gram-positive, Gram-negative, and fungal microbes - Yijing Wang; Huayang Sun; Zhen Wang; Yao Wang; Xin Li; Xiaoyu Han; Xin Zhao; Aifen Zhou; Wei-Min Wu (Chemical Engineering Journal, 2024)

Seasonal prediction of midsummer compound heat-humidity events over Southeast China - Tingting Han; Wanying Sun; Yao Zhi; Huijun Wang; Shangfeng Li; Zhicong Yin (Atmospheric Research, 2024)

Overexpression of a Malus baccata (L.) Borkh WRKY transcription factor gene MbWRKY65 increased the tolerance to cold and drought in transgenic tomato - Chunwen Yu; Anqi Yao; Xingguo Li; Wenhui Li; Ruina Gao; Yuqing Feng; Zhuxuan Li; Xinxin Guo; Lihua Zhang; Deguo Han (In Vitro Cellular & Developmental Biology - Plant, 2024)

Central role of Sigma-1 receptor in ochratoxin A-induced ferroptosis - Wenying Chen; Lingyun Han; Ruiran Yang; Hongwei Wang; Song Yao; Huiqiong Deng; Shuangchao Liu; Yao Zhou; Xiao Li Shen (Archives of Toxicology, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Adsorption and recovery of phosphate using sodium carbonate as co-precipitant synthesized La&Zr dual-metal modified material: Adsorption mechanism and practical application - Yuansi Hu; Yao Li; Yuhao Du; Bing Zhao; Mengli Chen; Xiaogang Tian; Sikai Chen; Meikun Fan; Han Zhang (Chemosphere, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A western Amazonian affinity in the periphery of the Nuna supercontinent for Mesoproterozoic basements in the southern Central Asian orogenic belt - Qian Liu; Yigui Han; Jinlong Yao; Jianhua Li; Peng Wang; Donghai Zhang; Guochun Zhao; Toshiaki Tsunogae (Precambrian Research, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

Dual-recognition “turn-off-on” fluorescent Biosensor triphenylamine-based continuous detection of copper ion and glyphosate applicated in environment and living system - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Han-Wen Cui; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2024)

A preliminary integrated analysis of regional paleoclimate variations in China over the past ∼ 21 ka - Huayu Lu; Yan Zhao; Xiangdong Yang; Haibing Wu; Cheng Zhao; Jingjing Wang; Xiaoyong Wang; Xueyuan Kuang; Xiaojian Zhang; Chunmei Ma; Fuzhi Lu; Xiayun Xiao; et al. (Global and Planetary Change, 2024)

Properties, extraction and purification technologies of Stevia rebaudiana steviol glycosides: A review - Chengxia Huang; Yang Wang; Cunshan Zhou; Xingyu Fan; Qiaolan Sun; Jingyi Han; Chenhui Hua; Yao Li; Yunwei Niu; Clinton Emeka Okonkwo; Deyang Yao; Linglin Song; et al. (Food Chemistry, 2024)

Separation of ovomucin from duck egg white and its “acid-tight /alkali-loose” self-supporting gel properties under different pH - Yao Yao; Yucheng Zhong; Han Li; Tiantian Liu; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Hydrocolloids, 2024)

Enhanced gut microbiota delivery of a model probiotic (Faecalibacterium prausnitzii): Layer-by-layer encapsulation using riboflavin-conjugated sodium alginate and glycol chitosan - Bo Qiu; Huijuan Jing; Shengyi Han; Shuobo Zhang; Furong Ba; Lvwan Xu; Siyuan Xie; Wang Gao; Yilun Huang; Hang Xiao; David Julian McClements; Björn Berglund; et al. (Food Hydrocolloids, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Biphasic Mo-based catalysts with abundant pores and rich heterostructures for high-efficient production of hydrogen in both alkaline and acidic media - Guangyan Tian; Kefeng Zhang; Minghang Li; Kailong Nie; Bingxue Yao; Wenqian Qu; Yan Li; Gaofeng Han; Wenbo Wang (Chemical Engineering Journal, 2024)

Solvent-vapor-triggered crystallization of a ZIF-90 membrane with versatile separation properties towards light hydrocarbons - Xu Wang; Rui Yao; Han Zhu; Zinan Zhang; Lifeng Zhang; Qiang Ma; Hua Jin; Yanshuo Li (Chemical Engineering Journal, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

An ensemble method based on weight voting method for improved prediction of slope stability - Yumin Chen; Zhongling Fu; Xiaofei Yao; Yi Han; Zhenxiong Li (Natural Hazards, 2024)

Neuroimage analysis using artificial intelligence approaches: a systematic review - Eric Jacob Bacon; Dianning He; N’bognon Angèle D’avilla Achi; Lanbo Wang; Han Li; Patrick Dê Zélèman Yao-Digba; Patrice Monkam; Shouliang Qi (Medical & Biological Engineering & Computing, 2024)

Abundance and health risk of bioaerosols in the coastal areas of Qingdao, China - Lingchong Yan; Ting Zhang; Shaohua Sun; Yongzhong Song; Chen Han; Yao Wang; Jianhua Qi; Xianguo Li; Dahai Zhang (Aerobiologia, 2024)

Schisandrin B protect inner hair cells from cisplatin by inhibiting celluar oxidative stress and apoptosis - Yao Li; Zhenzhen Liu; Jun Chen; Renfeng Wang; Xiaogang An; Chaoyong Tian; Han Yang; Dingjun Zha (Toxicology in Vitro, 2024)

Integrated multilevel investigation of photosynthesis revealed the algal response distinction to differentially charged nanoplastics - Saibo Liu; Jingheng Han; Linjie Yao; Huijun Li; Guorong Xin; Shih-Hsin Ho; Xiaochen Huang (Journal of Hazardous Materials, 2024)

Effects of combined drying techniques and cellulase hydrolysis on the nutritional value and sensory properties of shiitake mushrooms (Lentinus edodes) - Yao Li; Jingyi Han; Otu Phyllis Naa Yarley; Yujin Wang; Yang Wang; Ao Zhang; Xingyu Fan; Cunshan Zhou; Weiqiao Lv (Food Chemistry, 2024)

Augmenting the stability of soil aggregate carbon with nutrient management in worldwide croplands - Yini Wang; Yanzhong Yao; Bingbing Han; Bin Liu; Xiaozhong Wang; Lihua Ma; Xinping Chen; Zhaolei Li (Agriculture, Ecosystems & Environment, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Comparative study on the activation of peroxymonosulfate and peroxydisulfate by Ar plasma-etching CNTs for sulfamethoxazole degradation: Efficiency and mechanisms - Xuecong Zhao; Shiqi Liu; Yao Tong; Lei Sun; Qi Han; Li Feng; Liqiu Zhang (Chemosphere, 2024)

Microbial communities overwhelm environmental controls in explaining nitrous oxide emission in acidic soils - Shengwen Xu; Yongxiang Yu; Haoxin Fan; Nataliya Bilyera; Xiangtian Meng; Jiantao Xue; Zhong Lu; Zhihan Yang; Stephen J. Chapman; Fuyun Gao; Wenyan Han; Yaying Li; et al. (Soil Biology and Biochemistry, 2024)

Mitigating sediment cadmium contamination through combining PGPR Enterobacter ludwigii with the submerged macrophyte Vallisneria natans - Xiangfen Liu; Yao Guo; Yahua Li; Qianzheng Li; Lu Yao; Junqi Yu; Han Chen; Kaixuan Wu; Dongru Qiu; Zhenbin Wu; Qiaohong Zhou (Journal of Hazardous Materials, 2024)

Polydopamine-assisted immobilization of metallic nanoparticles confined regionally in bamboo microchannels as continuous-flow microreactors for enhanced catalysis - Sisi Yao; Dengkang Guo; Shenjie Han; Zongying Fu; Shaoyi Lyu; Jingpeng Li; Yun Lu (Chemical Engineering Journal, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Investigation on tunnelling-induced soil pressure changes, a modified trapdoor test study - Yao Li; Xing Dong; Xuchao Du; Zhanglong Guo; Houxian Chen; Ruida Han (Tunnelling and Underground Space Technology, 2024)

Fine particulate matter exposure and systemic inflammation: A potential mediating role of bioactive lipids - Wu Chen; Yiqun Han; Yifan Xu; Teng Wang; Yanwen Wang; Xi Chen; Xinghua Qiu; Weiju Li; Haonan Li; Yunfei Fan; Yuan Yao; Tong Zhu (Science of The Total Environment, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Early warning for thermal runaway in lithium-ion batteries during various charging rates: Insights from expansion force analysis - Kuijie Li; Long Chen; Xuebing Han; Xinlei Gao; Yao Lu; Depeng Wang; Shun Tang; Weixin Zhang; Weixiong Wu; Yuan-cheng Cao; Languang Lu; Jinyu Wen; et al. (Journal of Cleaner Production, 2024)

An electrochemical impedance spectroscopy study on ion-fouling of forward osmosis membranes - Lei Yao; Xiaojian Xu; Yang Gui; Yong Li; Zhe Chen; Jue Han; Yuan Liao (Desalination, 2024)

Surface hydroxyl groups mediated g-C3N4-Modified perovskite catalytic ozone oxidation interface activation and silicon salt resistance mechanism - Shengzhe Wang; Xianru Li; Weiyang Xue; Bin Gu; Peiwei Han; Chenxing Yao; Huangzhao Wei; Chenglin Sun (Chemical Engineering Journal, 2024)

Intelligent Off/On switchable electromagnetic wave absorbing material based on VO2 nanowires - Shuhui Liang; Huan Guan; Hainan Zhang; Xiangge Han; Jia Gao; Jiupeng Zhao; Shuliang Dou; Yao Li (Chemical Engineering Journal, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Identifying the plateau sodium storage behavior of hard carbon through the spin state - Bin Wang; Yazhen Yao; Wanli Wang; Yujie Xu; Yi Sun; Qiang Li; Han Hu; Mingbo Wu (Chemical Engineering Journal, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Flavonoids in vegetables: improvement of dietary flavonoids by metabolic engineering to promote health - Han Tao; Linying Li; Yuqing He; Xueying Zhang; Yao Zhao; Qiaomei Wang; Gaojie Hong (Critical Reviews in Food Science and Nutrition, 2024)

Enhancing phosphorus source apportionment in watersheds through species-specific analysis - Yuansi Hu; Mengli Chen; Jia Pu; Sikai Chen; Yao Li; Han Zhang (Water Research, 2024)

Tunable vortex bound states in multiband CsV3Sb5-derived kagome superconductors - Zihao Huang; Xianghe Han; Zhen Zhao; Jinjin Liu; Pengfei Li; Hengxin Tan; Zhiwei Wang; Yugui Yao; Haitao Yang; Binghai Yan; Kun Jiang; Jiangping Hu; et al. (Science Bulletin, 2024)

High contributions of fossil fuel sources to char-EC/soot-EC at a high-altitude site: Direct radiative effects and transport pathway - Huikun Liu; Qiyuan Wang; Yao Qu; Jie Tian; Li Li; Nan Ma; Yaqing Zhou; WeiKang Ran; Hui Su; Yongming Han; Giulia Pavese; Junji Cao (Fuel, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Molecular Characterization and Antibacterial Activity of a G-Type Lysozyme in Yellow Drum (Nibea albiflora) - Yao Xiao; Jiacheng Li; Qianqian Tian; Baolan Wu; Fang Han (Journal of Ocean University of China, 2024)

Adaptive tracking guidance for powered aeroassisted orbital maneuver under system uncertainties and input constraints - Qijia Yao; Qing Li; Hongwei Han; Jilin Chen (Advances in Space Research, 2024)

Regime shift of the leading mode of winter surface wind speed in northwest China in 2003/04 and its possible link with Barents–Kara sea ice - Yong Wang; Zi‐Han Zhou; Xin‐Yu Liu; Cheng‐Hai Wang; Dong Xiao; Wen‐Yao Li; Hao‐Jun Qin (International Journal of Climatology, 2024)
Using the ERA‐5 reanalysis datasets, NCEP/NCAR sea ice concentration (SIC) and observed winter surface wind speed (WSWS) in northwest China during 1979–2020, this study examined the regime shift of the leading mode of observed WSWS in northwest China and investigated its possible link with the winter Barents–Kara Sea (BKS) SIC. The leading mode of observed WSWS in northwest China showed negative anomalies in southern and northeastern Xinjiang, Gansu, western and northern Shaanxi Provinces, and positive anomalies in northwestern and middle Xinjiang, Qinghai and Ningxia Provinces. The signs of WSWS in the leading mode is generally opposite to their trends during 1979–2020. Leading principal component (PC1) of observed WSWS in northwest China underwent an obvious decreasing regime shift in 2003/04, as well as the winter BKS SIC. There are significant correlations between PC1 and BKS SIC on both interdecadal and interannual timescales. Decadal decrease of BKS SIC is accompanied with a positive phase of Scandinavia pattern (SP) with positive anomalies of 500‐hPa geopotential height over subtropical North Atlantic, Arctic‐Ural region and southern Asia, and negative anomalies over northern North Atlantic‐West Europe and Siberia regions. BKS SIC and SP significantly influenced the Northern China Wind Index (NCWI) at 200 hPa on interdecadal timescale, which was related to the PC1 on both interdecadal and interannual timescales after removing the signal of Arctic Oscillation. Meridional configuration of Siberian cyclonic anomaly and southern Asian anticyclonic anomaly associated with the winter BKS SIC could enhance the intensity of NCWI, which favoured the increase of observed WSWS in northwest China and thereby may contribute to the regime shift in 2003/04 of the leading mode. However, there were still some stations showing decreasing regime shift, which mainly located at the region of steeping terrain. These decreasing changes of WSWS may be related to circumfluence effect of terrain, urbanization and local microclimate, and these reasons still need further detailed study.

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Hydrate formation and deposition behaviors with kinetic inhibitors under pseudo multiphase flow - Lunxiang Zhang; Henglong Zou; Bingyue Han; Chen Lang; Haiyuan Yao; Qingping Li; Lei Yang; Jiafei Zhao; Yongchen Song (Fuel, 2024)

Exploring the influence of chemical state of Cu species on CO-SCR performance in spinel-type CuM2O4 (M = Co, Mn, Fe, Ni, and Cr): The synergy between Cu2+ and surface oxygen vacancy - Qi Jin; Li Han; Ning Li; Tiantian Zhang; Erhao Gao; Meng Yao; Shuiliang Yao; Zuliang Wu; Jing Li; Jiali Zhu; Wei Wang (Fuel, 2024)

Emissions of polycyclic aromatic hydrocarbons in PM2.5 emitted from motor vehicles exhaust (PAHs-PM2.5-MVE) under the plateau with low oxygen content - Qinzuo Yao; Jianwu Shi; Xinyu Han; Senlin Tian; Jianhong Huang; Yingjie Li; Ping Ning (Atmospheric Environment, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

Disentangling the variability of symbiotic nitrogen fixation rate and the controlling factors - Yanzhong Yao; Bingbing Han; Xunzhuo Dong; Yunyao Zhong; Shuli Niu; Xinping Chen; Zhaolei Li (Global Change Biology, 2024)
Symbiotic nitrogen (N) fixation (SNF), replenishing bioavailable N for terrestrial ecosystems, exerts decisive roles in N cycling and gross primary production. Nevertheless, it remains unclear what determines the variability of SNF rate, which retards the accurate prediction for global N fixation in earth system models. This study synthesized 1230 isotopic observations to elucidate the governing factors underlying the variability of SNF rate. The SNF rates varied significantly from 3.69 to 12.54 g N m −2 year −1 across host plant taxa. The traits of host plant (e.g. biomass characteristics and taxa) far outweighed soil properties and climatic factors in explaining the variations of SNF rate, accounting for 79.0% of total relative importance. Furthermore, annual SNF yield contributed to more than half of N uptake for host plants, which was consistent across different ecosystem types. This study highlights that the biotic factors, especially host plant traits (e.g. biomass characteristics and taxa), play overriding roles in determining SNF rate compared with soil properties. The suite of parameters for SNF lends support to improve N fixation module in earth system models that can provide more confidence in predicting bioavailable N changes in terrestrial ecosystems.

Innovation and development of the aquaculture nutrition research and feed industry in China - Xianyong Bu; Yueru Li; Wencong Lai; Chuanwei Yao; Yongtao Liu; Zhen Wang; Zengqi Zhao; Shangzhe Han; Jianlong Du; Xin Yao; Kangsen Mai; Qinghui Ai (Reviews in Aquaculture, 2024)
Aquaculture in China has undergone significant evolution in recent decades, transitioning from traditional practices to a vital food production industry. Alongside the rapid growth of aquaculture in China, aquafeed production continues to expand swiftly. This review attempts to establish an overview of the history and achievements in aquaculture nutrition research and feed industry in China. The development of scientific concept and methodology, especially the advanced molecular biology technology guarantees the shift from traditional nutrition to molecular nutrition, and subsequently to precision nutrition in aquaculture nutrition research. This evolution has facilitated the formulation of effective strategies to enhance the growth, health and product quality of aquatic animals. The advancements of aquaculture nutrition research and feed industry have also been propelled by innovative research concepts rooted in principles such as the health and safety of aquatic animals, the quality of aquatic products, resource conservation and environmental friendliness, and the advancements in key processing technologies within the aquafeed industry. The future perspectives of the aquaculture nutrition research and feed industry in China are also proposed. The present work aims to provide a reference for promoting the development of aquaculture nutrition research and feed industry in China.

Effects of storm runoff on the spatial–temporal variation and stratified water quality in Biliuhe Reservoir, a drinking water reservoir - Weijia Li; Xiaoqiang Chen; Shiguo Xu; Tianxiang Wang; Dongning Han; Yao Xiao (Environmental Science and Pollution Research, 2024)

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Deciphering the effects of hydrological, biogeochemical and anthropogenic factors on nitrogen species in a subtropical watershed using multiple isotopes - Xiuli Yan; Xiaolan Guo; Anqi Yao; Hongyan Bao; Da-Wei Li; Jr-Chuan Huang; Junwen Wu; Li-Li Han; Shuh-Ji Kao (Journal of Hydrology, 2024)

A molecular dynamics simulation study on the recovery performance of aged asphalt binder by waste vegetable oil rejuvenators - Bo Li; Jihong Han; Dingbang Wei; Haidong Ji; Tengfei Yao; Haopeng Wang; Jie Han; Yunpeng Zhang (Journal of Cleaner Production, 2024)

Investigating the effect of anode materials on the performance and microbial community in an integrated chamber-free microbial fuel cell - Taotao Zhang; Yahui Chen; Yongyun Li; Peng Chen; Haitao Ma; Pengju Han; Can Wang; Wei Liu; Yao Wang; Renwei Qing; Fei Xu (Fuel, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

A high-efficient protoplast transient system for screening gene editing elements in Salvia miltiorrhiza - Jin Shao; Bowen Peng; Yaojie Zhang; Xin Yan; Xinghao Yao; Xinyi Hu; Ling Li; Xueqing Fu; Han Zheng; Kexuan Tang (Plant Cell Reports, 2024)

Novel dual-responsive hydrogel composed of polyacrylamide/Fe-MOF/zinc finger peptide for construction of electrochemical sensing platform - Youyu Li; Jiejie Feng; Tao Yao; Hongliang Han; Zhanfang Ma; Haijun Yang (Analytica Chimica Acta, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Study on the suppression characteristics and mechanism of ABC powder on pulverized coal explosion based on the analysis of thermal decomposition characteristics and reaction kinetics - Bingyou Jiang; Qi Yao; Mingqing Su; Jingjing Li; Kunlun Lu; Dawei Ding; Han Hong (Process Safety and Environmental Protection, 2024)

Upper Triassic (middle Norian) conodont biostratigraphy succession from Qamdo, eastern Tibet - Zhengyi Lyu; Martyn L. Golding; He Zhao; Huazhou Yao; Xiangdong Wang; Lei Zhang; Yangui Li; Chen Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

Fish entrainment model for decision support in ecosystem management: A case study from China's Maling Reservoir - Qianqian Wang; Yu Han; Meixia Bao; Pengcheng Li; Yike Li; Wenming Zhang; Weiwei Yao (Ecohydrology & Hydrobiology, 2024)

Peroxymonosulfate activation by boron doped C3N5 metal-free materials with n → π* electronic transitions for tetracycline degradation under visible light: Insights into the generation of reactive species - Yao Tong; Shaojiang Huang; Xuecong Zhao; Yang Yang; Li Feng; Qi Han; Liqiu Zhang (Chemical Engineering Journal, 2024)

Novel oxygen vacancy-rich Bi2MoO6-SOVs/MgFe2O4 S-scheme heterojunction piezo-photocatalytic for efficient degradation of norfloxacin and theoretical calculations - Hainan Wei; Fanming Meng; Han Zhang; Wenqing Yu; Jialong Li; Sheng Yao (Chemical Engineering Journal, 2024)

Thawing and Softening of Frozen Sandstone by Microwave Irradiation - Li Han; Hailiang Jia; Yuanhong Dong; Yao Wei; Xianjun Tan (Rock Mechanics and Rock Engineering, 2024)

Direct and indirect photodegradation of bisphenol A in the presence of natural water components - Yao Han; Lijun Li; Lu Jin; Rong Zhou; Yayu Li; Weiwen Jing (Environmental Geochemistry and Health, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Microbial traits dictate soil necromass accumulation coefficient: A global synthesis - Bingbing Han; Yanzhong Yao; Yini Wang; Xiaoxuan Su; Lihua Ma; Xinping Chen; Zhaolei Li (Global Ecology and Biogeography, 2024)
Aim The accumulation of microbial necromass carbon has gained increasing attention due to its slow decomposition. However, it remains unclear what induces the accumulation of microbial necromass carbon via reiterated community turnover on large spatial scales. This study explores the characteristics of soil necromass carbon accumulation in terrestrial ecosystems. Location Global. Time Period Contemporary (1999–2022). Major Taxa Studied Soil microorganisms. Methods A dataset was compiled using 993 observations from 82 peer‐reviewed papers on the effects of coefficients of microbial necromass accumulation (hereafter NAC) in equilibrium. Linear mixed‐effect models and structural equation models were used to ascertain the controlling factors of the NAC. Results The average NAC was higher in croplands (28.2) and forests (26.8) than in grasslands (21.1). Edaphic factors seemingly affected the NAC, which was lower in soils with high pH and clay content on a global scale. Biotic factors, particularly those related to living microorganism abundance and microbial biomass nitrogen content, were the pivotal drivers of NAC and accounted for approximately 43.6% of its geographic variability. More organic carbon was likely to be preserved in soil with a higher NAC, regardless of ecosystem type. Conclusions Novel findings regarding the overriding controls for the living microorganism abundance and microbial biomass nitrogen that drive the NAC highlight an urgent need for viable strategies to manipulate microbial attributes for enhancing carbon sequestration.

Relative importance between nitrification and denitrification to N 2 O from a global perspective - Bingbing Han; Yanzhong Yao; Bin Liu; Yini Wang; Xiaoxuan Su; Lihua Ma; Dunyi Liu; Shuli Niu; Xinping Chen; Zhaolei Li (Global Change Biology, 2024)
Nitrous oxide (N 2 O) is a potent greenhouse gas, and its mitigation is a pressing task in the coming decade. However, it remains unclear which specific process between concurrent nitrification and denitrification dominates worldwide N 2 O emission. We snagged an opportunity to ascertain whence the N 2 O came and which were the controlling factors on the basis of 1315 soil N 2 O observations from 74 peer‐reviewed articles. The average N 2 O emission derived from nitrification (N 2 O n ) was higher than that from denitrification (N 2 O d ) worldwide. The ratios of nitrification‐derived N 2 O to denitrification‐derived N 2 O, hereof N 2 O n :N 2 O d , exhibited large variations across terrestrial ecosystems. Although soil carbon and nitrogen content, pH, moisture, and clay content accounted for a part of the geographical variations in the N 2 O n :N 2 O d ratio, ammonia‐oxidizing microorganisms (AOM):denitrifier ratio was the pivotal driver for the N 2 O n :N 2 O d ratios, since the AOM:denitrfier ratio accounted for 53.7% of geographical variations in N 2 O n :N 2 O d ratios. Compared with natural ecosystems, soil pH exerted a more remarkable role to dictate the N 2 O n :N 2 O d ratio in croplands. This study emphasizes the vital role of functional soil microorganisms in geographical variations of N 2 O n :N 2 O d ratio and lays the foundation for the incorporation of soil AOM:denitrfier ratio into models to better predict N 2 O n :N 2 O d ratio. Identifying soil N 2 O derivation will provide a global potential benchmark for N 2 O mitigation by manipulating the nitrification or denitrification.

Cephalopod-inspired polymer composites with mechanically tunable infrared properties - Bin Yao; Xinwei Xu; Zhubing Han; Wenhan Xu; Guang Yang; Jing Guo; Guixin Li; Qing Wang; Hong Wang (Science Bulletin, 2023)

Inoculation of cold-adapted microbial consortium screened from alpine meadows promotes the growth of mixed grasses by changing soil properties and enzyme activity - Jiali Chai; Xian Wang; Xiaoting Liu; Changning Li; Jiangru Han; Tuo Yao (Rhizosphere, 2023)

Unveiling targeted spatial metabolome of rice seed at the dough stage using Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry imaging - Yao Zhao; Jitao Hu; Yilin Zhang; Han Tao; Linying Li; Yuqing He; Xueying Zhang; Chi Zhang; Gaojie Hong (Food Research International, 2023)

Analysis of research status and trends on marine benthic dinoflagellate toxins: A bibliometric study based on web of science database and VOSviewer - Jing-Qian Tang; Qian-Hui Shen; Yao-Yao Han; Yang Wu; Xiang-Feng He; Da-Wei Li; Yong Huang (Environmental Research, 2023)

Janus photothermal adsorbent for solar-powered simultaneous uranium extraction and co-production of freshwater and sea salt from seawater - Mengtao Fu; Li Han; Chen Huang; Lin Ma; Yunyou Yao; Kang Chen; Peng Sun; Haiyang Shao; Minghong Wu; Bowu Zhang; Hongjuan Ma (Chemical Engineering Journal, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Critical review on modified floating photocatalysts for emerging contaminants removal from landscape water: problems, methods and mechanism - Xiaoning Fu; Guangzhu Zhou; Jianping Li; Qiuhui Yao; Zuozhen Han; Rongchao Yang; Xi Chen; Yuanhao Wang (Chemosphere, 2023)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Corrigendum to “Comparative metabolomics of flavonoids in twenty vegetables reveal their nutritional diversity and potential health benefits” [Food Res. Int. 164 (2023) 112384] - Han Tao; Yao Zhao; Linying Li; Yuqing He; Xueying Zhang; Ying Zhu; Gaojie Hong (Food Research International, 2023)

Cobalt doped nitrogen-vacancies-rich C3N5 with optimizing local electron distribution boosts peroxymonsulfate activation for tetracycline degradation: Multiple electron transfer mechanisms - Yao Tong; Peng Gao; Jiacan Xu; Shiqi Liu; Yang Yang; Yang Wang; Li Feng; Qi Han; Yongze Liu; Liqiu Zhang (Chemosphere, 2023)

Effects of organic pollutants on struvite crystallization kinetics and the molecular mechanism of inhibition on crystal growth - Menghui Yao; Lingyu Wang; Jiahao Wei; Zhenkai Cen; Xuemei Wei; Guoqi Yu; Hualiang Shen; Runpu Shen; Dandan Han; Mingyang Chen; Kangli Li; Junbo Gong (Science of The Total Environment, 2023)

Robust anti-disturbance fault-tolerant control of ship-board platforms with multiplicative actuator faults and unknown disturbances - Qingtao Gong; Zhipeng Liu; Xin Hu; Yao Teng; Kangqiang Li; Guojie Han (Ocean Engineering, 2023)

A combined hydrodynamic model and deep learning method to predict water level in ungauged rivers - Gang Li; Haoyu Zhu; Hongfu Jian; Wei Zha; Jiang Wang; Zhangkang Shu; Siyang Yao; Huiming Han (Journal of Hydrology, 2023)

Microbial electron flow promotes naphthalene degradation in anaerobic digestion in the presence of nitrate electron acceptor: Focus on electron flow regulation and microbial interaction succession - Yilin Yao; Yanhao Wei; Jingyi Li; Ruotong Han; Chuanyong Jing; Rutao Liu; Qigui Niu (Journal of Hazardous Materials, 2023)

Cloning, subcellular localization and antibacterial functional analysis of NK-lysin in yellow drum (Nibea albiflora) - Ying Huang; Baolan Wu; Yao Yang; Wanbo Li; Fang Han (Fish & Shellfish Immunology, 2023)

Pollution characteristics, ecological and health risks of herbicides in a drinking water source and its inflowing rivers in North China - Yilin Li; Ruiyao Guo; Xiaoge Liang; Bo Yao; Shuwen Yan; Yanan Guo; Yonghui Han; Jiansheng Cui (Environmental Pollution, 2023)

Unraveling the promotional effects of K-doping on the mobility of surface oxygen species of CoCr2O4 for improved formaldehyde catalytic oxidation: The weakened metal-oxygen bond strength - Erhao Gao; Qi Jin; Tiantian Zhang; Li Han; Ning Li; Jiacheng Xu; Shuiliang Yao; Zuliang Wu; Jing Li; Jiali Zhu; Wei Wang (Chemical Engineering Journal, 2023)

Ultra-stable, waterproof and self-healing serpentine stretchable conductors based on WPU sheath-wrapped conductive yarn for stretchable interconnects and wearable heaters - Hui Yuan; Runzhou Jia; Hai Yao; Wei Wang; Kun Qian; Xulei Wu; Jing Li; Zhengtao Wang; Luying Lv; Menghong Han; Yuzhen Dong; Huatao Wang (Chemical Engineering Journal, 2023)

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Simultaneous Optimization of SWMM Parameters by the Dynamic System Response Curve with Multi-Objective Function - Yao Du; Qiongfang Li; Pengfei He; Zhenhua Zou; Zhengmo Zhou; Shuhong Xu; Xingye Han; Tianshan Zeng (Water Resources Management, 2023)

Modeling of breaching parameters for debris flow dams - He-chun Ruan; Hua-yong Chen; Xiao-qing Chen; Wan-yu Zhao; Jian-gang Chen; Tao Wang; Yao Jiang; Xi-an Wang; Xiang-ning Li; Xiao Li; Yun-han Yu (Journal of Mountain Science, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Spatiotemporal distribution and mechanism of Mesozoic magmatism in the South China Sea and its adjacent areas: insights from seismic, geochemical, and geochronological data - Song Zhu; Yongjian Yao; Jianglang Tang; Yanfei Han; Shantang Yi; Xuejie Li; Chupeng Yang (International Geology Review, 2023)

Exopolysaccharides synthesized by lactic acid bacteria: biosynthesis pathway, structure-function relationship, structural modification and applicability - Jinsong Wu; Xiangpeng Han; Meizhi Ye; Yao Li; Xi Wang; Qingping Zhong (Critical Reviews in Food Science and Nutrition, 2023)

Impacts of rainstorm characteristics on flood inundation mitigation performance of LID measures throughout an urban catchment - Zhengmo Zhou; Qiongfang Li; Pengfei He; Yao Du; Zhenhua Zou; Shuhong Xu; Xingye Han; Tianshan Zeng (Journal of Hydrology, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Biodegradation of p-hydroxybenzoic acid in Herbaspirillum aquaticum KLS-1 isolated from tailing soil: Characterization and molecular mechanism - Yi-Xi Li; Wei Lin; Yong-He Han; Yao-Qiang Wang; Tao Wang; Hong Zhang; Yong Zhang; Shan-Shan Wang (Journal of Hazardous Materials, 2023)

Dermal repeated dose toxicity study of the anti-breast cancer drug Formestane cream in Bama minipig - Shiyao Huang; Ziming Wu; Youyou Chen; Han Li; Linglin Zou; Alexander T. Teichmann; Yao Luo; Lifeng Zhang; Lanyang Gao (Food and Chemical Toxicology, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Residual status and source analysis of phthalate esters in Ulungur Lake, China - Manli Wang; Jianjiang Lu; Li Zhou; Youzhi Su; Han Yao; Min Li; Xiaowen Yin (Environmental Geochemistry and Health, 2023)

A comprehensive approach to quantify the source identification and human health risk assessment of toxic elements in park dust - Chang-Chen Huang; Li-Mei Cai; Yao-Hui Xu; Luo Jie; Guo-Cheng Hu; Lai-Guo Chen; Han-Zhi Wang; Xu-Bang Xu; Jing-Xian Mei (Environmental Geochemistry and Health, 2023)

A chemiluminescence method induced by microplasma jet for nitrites detection and the miniature detection system using smartphone - Yi Cai; Han Zhou; Wei Li; Cheng Yao; Jianhua Wang; Yong Zhao (Analytica Chimica Acta, 2023)

Analysis of internal flow characteristics and determination of the core structural parameters of a stellate labyrinth channel irrigation emitter - Yanfei Li; Xianying Feng; Xingchang Han; Yitian Sun; Yandong Liu; Ming Yao; Haiyang Liu; Qinghai He; Hui Li (Biosystems Engineering, 2023)

Ecohydraulic modelling to evaluate cascade dam construction impact and support fish habitat restoration - Qianqian Wang; Yu Han; Pengcheng Li; Wenming Zhang; Yihang Wang; Yuqian Xi; Weiwei Yao (Ecological Engineering, 2023)

Study on seepage characteristics and stress sensitivity of sandstone under cyclic water intrusion based on CT scanning technique - Zhe Qin; Wenlong Pang; Weizheng Mao; Jihuan Han; Zhiwen Li; Yujing Yao (Bulletin of Engineering Geology and the Environment, 2023)

Global variations and controlling factors of anammox rates - Yanzhong Yao; Bingbing Han; Bin Liu; Yini Wang; Xiaoxuan Su; Lihua Ma; Tong Zhang; Shuli Niu; Xinping Chen; Zhaolei Li (Global Change Biology, 2023)
Soil anammox is an environmentally friendly way to eliminate reactive nitrogen (N) without generating nitrous oxide. Nevertheless, the current earth system models have not incorporated the anammox due to the lack of parameters in anammox rates on a global scale, limiting the accurate projection for N cycling. A global synthesis with 1212 observations from 89 peer‐reviewed papers showed that the average anammox rate was 1.60 ± 0.17 nmol N g −1 h −1 in terrestrial ecosystems, with significant variations across different ecosystems. Wetlands exhibited the highest rate (2.17 ± 0.31 nmol N g −1 h −1 ), followed by croplands at 1.02 ± 0.09 nmol N g −1 h −1 . The lowest anammox rates were observed in forests and grasslands. The anammox rates were positively correlated with the mean annual temperature, mean annual precipitation, soil moisture, organic carbon (C), total N, as well as nitrite and ammonium concentrations, but negatively with the soil C:N ratio. Structural equation models revealed that the geographical variations in anammox rates were primarily influenced by the N contents (such as nitrite and ammonium) and abundance of anammox bacteria, which collectively accounted for 42% of the observed variance. Furthermore, the abundance of anammox bacteria was well simulated by the mean annual precipitation, soil moisture, and ammonium concentrations, and 51% variance of the anammox bacteria was accounted for. The key controlling factors for soil anammox rates differed from ecosystem type, for example, organic C, total N, and ammonium contents in croplands, versus soil C:N ratio and nitrite concentrations in wetlands. The controlling factors in soil anammox rate identified by this study are useful to construct an accurate anammox module for N cycling in earth system models.

Molecular identification and functional analysis of Niemann-Pick type C2 proteins，carriers for semiochemicals and other hydrophobic compounds in the brown dog tick, Rhipicephalus linnaei - Dejuan Liang; Huaqing Chen; Liping An; Yao Li; Peizhen Zhao; Archana Upadhyay; Bill S. Hansson; Jianguo Zhao; Qian Han (Pesticide Biochemistry and Physiology, 2023)

MxFRO4 confers iron and salt tolerance through up-regulating antioxidant capacity associated with the ROS scavenging - Chuankun Ren; Guijie Luo; Xingguo Li; Anqi Yao; Wanda Liu; Lihua Zhang; Yu Wang; Wenhui Li; Deguo Han (Journal of Plant Physiology, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

pH-responsive switchable deep eutectic solvents to mediate pretreatment method for trace analysis of triazole fungicides in peel wastes - Jingyu Zhang; Zhihui Zhang; Liping Yao; Mingrong Qian; Zuguang Li; Yulin Han; Shanshan Bai; Mawrong Lee (Food Chemistry, 2023)

Poly-γ-glutamic acid-producing Bacillus velezensis fermentation can improve the feed properties of soybean meal - Han Hu; Caiyun Wu; Fanglan Ge; Yao Ren; Wei Li; Jiao Li (Food Bioscience, 2023)

Excessive ER-phagy contributes to ochratoxin A-induced apoptosis - Huiqiong Deng; Wenying Chen; Boyang Zhang; Yiwen Zhang; Lingyun Han; Qipeng Zhang; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Fluorine/sulfur-comodulated covalent organic frameworks cathode for high-performance lithium ion batteries - Tianyu Qiu; Wensi Tang; Xu Han; Yang Li; Zhiwen Chen; Ruiqi Yao; Yingqi Li; Yonghui Wang; Yangguang Li; Huaqiao Tan (Chemical Engineering Journal, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Spatialization of Chinese R-410A emissions from the room air-conditioning sector - Pengcheng Wu; Li Zhang; Bo Yao; Bofeng Cai; Yifang Zhu; Hui Liu; Pengling Wang; Lisha Liu; Yanwei Dou; Han Yan; Yijun Liu; Zixuan Xie; et al. (Environment, Development and Sustainability, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Levels, distribution, childhood exposure assessment, and influencing factors of polybrominated diphenyl ethers (PBDEs) in household dust from nine cities in China - Jing Qi; Xiaoli Wang; Lin Fan; Shuhan Gong; Xinqi Wang; Chong Wang; Li Li; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Fertilizer-induced N2O and NO emissions in tea gardens and the main controlling factors: A recent three-decade data synthesis - Haiyang Yu; Xing Han; Xuechen Zhang; Xiangtian Meng; Zhengfu Yue; Xinhui Liu; Ningguo Zheng; Yaying Li; Yongxiang Yu; Huaiying Yao (Science of The Total Environment, 2023)

Late Neoproterozoic meta-gabbro in northeastern margin of the Yangtze Block: Magmatism related to late breakup of the Rodinia - Chao Wang; Yang Li; Yigui Han; Guochun Zhao; Houchun Guan; Yao Wang; Song Wang; Liyuan Xia (Precambrian Research, 2023)

Predominance of positive priming effects induced by algal and terrestrial organic matter input in saline lake sediments - Jian Yang; Mingxian Han; Beichen Wang; Bingfu Yao; Zenghui Wu; Xinyi Li; Li Liu; Hailiang Dong; Hongchen Jiang (Geochimica et Cosmochimica Acta, 2023)

Bionic multifunctional ultra-linear strain sensor, achieving underwater motion monitoring and weather condition monitoring - Jianhao Li; Zhongwen Yao; Xiangxiang Zhang; Ze Wang; Linpeng Liu; Xiaoning Yang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2023)

Genome-wide analysis of genetic pleiotropy and causal genes across three age-related ocular disorders - Xueming Yao; Hongxi Yang; Han Han; Xuejing Kou; Yuhan Jiang; Menghan Luo; Yao Zhou; Jianhua Wang; Xutong Fan; Xiaohong Wang; Mulin Jun Li; Hua Yan (Human Genetics, 2023)

Role of prebiotics in enhancing the function of next-generation probiotics in gut microbiota - Yiqiu Fei; Zuobing Chen; Shengyi Han; Shuobo Zhang; Tianfang Zhang; Yanmeng Lu; Björn Berglund; Hang Xiao; Lanjuan Li; Mingfei Yao (Critical Reviews in Food Science and Nutrition, 2023)

Levels, distribution, sources and children health risk of PAHs in residential dust: A multi-city study in China - Xinqi Wang; Xiaoli Wang; Jing Qi; Shuhan Gong; Chong Wang; Li Li; Lin Fan; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Development and characterization of yeast-incorporated coating films for improving the postharvest shelf-life of snap beans - Xinmao Li; Hossein Ghanizadeh; Zhengyuan Han; Tiantian Li; Yinghui Li; Zhitao Dou; Youwen Qiu; Xiuling Chen; Yao Zhang; Jiayin Liu; Aoxue Wang (Postharvest Biology and Technology, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Formation of the Zengmu and Beikang Basins, and West Baram Line in the southwestern South China Sea margin - Bing Han; Zhongxian Zhao; Xiaofang Wang; Zhen Sun; Fucheng Li; Benduo Zhu; Yongjian Yao; Liqiang Liu; Tianyue Peng; Genyuan Long (Journal of Oceanology and Limnology, 2023)

Crystal-modeler: A tool for geometric analysis and three-dimensional modeling of crystal forms based on rectangular coordinates in space - Huixia Chao; Yue Li; Weihua Yao; Xin Han; Ran Wang (Earth Science Informatics, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Optical bulk-boundary dichotomy in a quantum spin Hall insulator - Junfeng Han; Pengcheng Mao; Hailong Chen; Jia-Xin Yin; Maoyuan Wang; Dongyun Chen; Yongkai Li; Jingchuan Zheng; Xu Zhang; Dashuai Ma; Qiong Ma; Zhi-Ming Yu; et al. (Science Bulletin, 2023)

Comparative metabolomics of flavonoids in twenty vegetables reveal their nutritional diversity and potential health benefits - Han Tao; Yao Zhao; Linying Li; Yuqing He; Xueying Zhang; Ying Zhu; Gaojie Hong (Food Research International, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Comprehensive study of energy and water exchange over the Tibetan Plateau: A review and perspective: From GAME/Tibet and CAMP/Tibet to TORP, TPEORP, and TPEITORP - Yaoming Ma; Tandong Yao; Lei Zhong; Binbin Wang; Xiangde Xu; Zeyong Hu; Weiqiang Ma; Fanglin Sun; Cunbo Han; Maoshan Li; Xuelong Chen; Jiemin Wang; et al. (Earth-Science Reviews, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

A Buffeting-Net for buffeting response prediction of full-scale bridges - Shujin Laima; Hui Feng; Hui Li; Yao Jin; Feiyang Han; Wencheng Xu (Engineering Structures, 2023)

Study on axial compression performance of double steel plate-concrete composite walls with stiffening ribs and tie plates - Yue Yang; Bin Wu; Yang-Ping Yao; Li-Yan Xu; Dong Zhang; Song-Han Wang (Engineering Structures, 2023)

An injectable, self-healing composite hydrogel with enhanced near-infrared photo-antibacterial therapeutic effects for accelerated wound healing - Jiameng Wang; Hao Cheng; Weiyi Chen; Peide Han; Xiaohong Yao; Bin Tang; Wangping Duan; Pengcui Li; Xiaochun Wei; Paul K. Chu; Xiangyu Zhang (Chemical Engineering Journal, 2023)

Fabrication and Characterization of a MnO2/Ti3C2Tx Based Gas Sensor for Highly Sensitive and Selective Detection of Lung Cancer Marker Hexanal - Yu Yao; Zhanhong Li; Yutong Han; Lili Xie; Xueling Zhao; Zhigang Zhu (Chemical Engineering Journal, 2023)

A robust glacial lake outburst susceptibility assessment approach validated by GLOF event in 2020 in the Nidu Zangbo Basin, Tibetan Plateau - Dahong Zhang; Gang Zhou; Wen Li; Lei Han; Shiqiang Zhang; Xiaojun Yao; Hongyu Duan (CATENA, 2023)

Corrigendum to “Climate, topography and anthropogenic effects on desert greening: A 40-year monitoring in the Tengger desert, northern China” [Catena 209(2) (2021) 105851] - Li Wang; Yanning Qiu; Zhiyong Han; Chi Xu; Shuang-Ye Wu; Yao Wang; Milena Holmgren; Zhiwei Xu (CATENA, 2023)

Spatio-temporal changes in daily extreme precipitation for the Lancang–Mekong River Basin - Qiongfang Li; Tianshan Zeng; Qihui Chen; Xingye Han; Xi Weng; Pengfei He; Zhengmo Zhou; Yao Du (Natural Hazards, 2023)

Viperin deficiency promotes dendritic cell activation and function via NF-kappaB activation during Mycobacterium tuberculosis infection - Xinying Zhou; Hui Xu; Qianna Li; Qi Wang; Honglin Liu; Yingqi Huang; Yao Liang; Linmiao Lie; Zhenyu Han; Yaoxin Chen; Yulan Huang; Wenle Zhou; et al. (Inflammation Research, 2023)
Objectives and design Dendritic cells (DCs) are one of the key immune cells in bridging innate and adaptive immune response against Mycobacterium tuberculosis (Mtb) infection. Interferons (IFNs) play important roles in regulating DC activation and function. Virus-inhibitory protein, endoplasmic reticulum-associated, interferon-inducible (Viperin) is one of the important IFN-stimulated genes (ISGs), and elicits host defense against infection. Methods We investigated the effects and mechanisms of Viperin on DC activation and function using Viperin deficient bone marrow-derived dendritic cells (BMDCs) during Mtb infection. Results Viperin deficiency enhanced phagocytic activity and increased clearance of Mtb in DCs, produced higher abundance of NO, cytokine including interleukin-12 (IL-12), Tumor necrosis factor-α (TNF- α ), IL-1 β , IL-6 and chemokine including CXCL1, CXCL2 and CXCL10, elevated MHC I, MHC II and co-stimulatory molecules expression, and enhanced CD4 + and CD8 + T cell responses. Mechanistically, Viperin deficiency promoted DC activation and function through NF-κB p65 activation. NF-κB p65 inhibitor prevented cytokine and chemokine production, and co-stimulatory molecules expression promoted by Viperin deficiency. Conclusions These results suggest that Mtb induced Viperin expression could impair the activation of host defense function of DCs and DC-T cell cross talk during Mtb infection. This research may provide a potential target for future HDT in TB therapy.

Plasmon resonance enhanced palygorskite-based composite toward the photocatalytic reformation of cellulose biomass under full spectrum - Xuhua Ye; Minghui Zhong; Ziwen Cao; Chaoya Han; Aiqin Wang; Chao Yao; Xiazhang Li (Applied Clay Science, 2023)

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Facial emotion perception abilities are related to grey matter volume in the culmen of cerebellum anterior lobe in drug-naïve patients with first-episode schizophrenia - Xiaoxin Zhao; Jingjing Yao; Yiding Lv; Xinyue Zhang; Chongyang Han; Lijun Chen; Fangfang Ren; Qun Zhou; Zhuma Jin; Yuan Li; Yasong Du; Yuxiu Sui (Brain Imaging and Behavior, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

A Highly Selective Fluorescent Probe for the Detection of Nitroreductase Based on a Naphthalimide Scaffold - Han Li; Feng Jintao; Zhen Wang; Yan Jia; Peng Li; Cuixia Yao; Zongjin Qu (Journal of Fluorescence, 2022)

Transcriptome analysis reveals the effects of strigolactone on shoot regeneration of apple - Sumeera Asghar; Yao Xiong; Meng Che; Xingqiang Fan; Hui Li; Yi Wang; Xuefeng Xu; Wei Li; Zhenhai Han (Plant Cell Reports, 2022)

Convergence study of water pollution emission intensity in China: evidence from spatial effects - Yixuan Han; Nan Li; Hailin Mu; Rong Guo; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

The Nature and Predictability of the East Asian Extreme Cold Events of 2020/21 - Guokun Dai; Chunxiang Li; Zhe Han; Dehai Luo; Yao Yao (Advances in Atmospheric Sciences, 2022)

Study on Reasonable Coal Pillar Width of Gob-Side Roadway Excavating with Multi-Layer Hard Roof in Western Deep Mine - Changliang Han; Houqiang Yang; Nong Zhang; Xudong Li; Yitao Liu; Wentao Liu; Wei Yao (Geotechnical and Geological Engineering, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Correction to: Determination of interactions of ferrihydrite‑humic acid‑Pb (II) system - Zhuanjun Zhao; Liwei Yao; Jie Li; Xiangbang Ma; Liangwei Han; Zhiyuan Lin; Shuqi Guan (Environmental Science and Pollution Research, 2022)

Determination of interactions of ferrihydrite-humic acid-Pb (II) system - Zhuanjun Zhao; Liwei Yao; Jie Li; Xiangbang Ma; Liangwei Han; Zhiyuan Lin; Shuqi Guan (Environmental Science and Pollution Research, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

Susceptibility of patients with chronic obstructive pulmonary disease to heart rate difference associated with the short-term exposure to metals in ambient fine particles: A panel study in Beijing, China - Ke Gao; Xi Chen; Xiaoying Li; Hanxiyue Zhang; Mengxiao Luan; Yuan Yao; Yifan Xu; Teng Wang; Yiqun Han; Tao Xue; Junxia Wang; Mei Zheng; et al. (Science China Life Sciences, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Optimization of the factors affecting droplet deposition in rice fields by rotary unmanned aerial vehicles (UAVs) - Shuang Guo; Jiyu Li; Weixiang Yao; Xiaodan Hu; Xu Wei; Bo Long; Han Wu; Huifen Li (Precision Agriculture, 2021)

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

Overexpression of MbERF12, an ERF gene from Malus baccata (L.) Borkh, increases cold and salt tolerance in Arabidopsis thaliana associated with ROS scavenging through ethylene signal transduction - Deguo Han; Jiaxin Han; Tianlong Xu; Xingguo Li; Chunya Yao; Tiemei Li; Xiaohan Sun; Xinhui Wang; Guohui Yang (In Vitro Cellular & Developmental Biology - Plant, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

An object-based graph model for unsupervised change detection in high resolution remote sensing images - Junzheng Wu; Biao Li; Yao Qin; Weiping Ni; Han Zhang (International Journal of Remote Sensing, 2021)

Correction to: Activation of Sigma-1 Receptor Enhanced Pericyte Survival Via the Interplay between Apoptosis and Autophagy: Implications for Blood–Brain Barrier Integrity in Stroke - Yuan Zhang; Xiaotian Zhang; Qiangqiang Wei; Shuo Leng; Cai Li; Bing Han; Ying Bai; Huibin Zhang; Honghong Yao (Translational Stroke Research, 2021)

Genetic mapping reveals BjRf as a candidate gene controlling fertility restoration of the oxa CMS in Brassica juncea - Qiqi Cheng; Peijie Yao; Hui Li; Yiming Han; Kejing Xu; Shuangping Heng; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2021)

Antimicrobial nanomedicine for ocular bacterial and fungal infection - Wenjie Fan; Haijie Han; Yaoyao Chen; Xiaobo Zhang; Yifan Gao; Su Li; Qiao Jin; Jian Ji; Ke Yao (Drug Delivery and Translational Research, 2021)

Wheat-root associated prokaryotic community: interplay between plant selection and location - Yuyin Zheng; Zhihan Feng; Jialong Wang; Xiaoman Huang; Li Lei; Xue Zhang; Huili Cao; Dandan Fan; Minjie Yao; Dejun Han; Xiangzhen Li (Plant and Soil, 2021)

Deep Learning Model for the Automated Detection and Histopathological Prediction of Meningioma - Hua Zhang; Jiajie Mo; Han Jiang; Zhuyun Li; Wenhan Hu; Chao Zhang; Yao Wang; Xiu Wang; Chang Liu; Baotian Zhao; Jianguo Zhang; Kai Zhang (Neuroinformatics, 2021)

Green-synthesized nanosize Mont-supported Fe0 via tea extract for enhanced transport and in situ remediation of Pb(II) in soil - Han Yang; Zhi Ye; Fang Feng; Nan Xu; Jing Yang; Zihan Yao; Zuling Li; Jianping Chen (Journal of Soils and Sediments, 2021)

The Effects of Metal Exposures on Charlson Comorbidity Index Using Zero-Inflated Negative Binomial Regression Model: NHANES 2011–2016 - Hantong Zhao; Yingan Pan; Changcong Wang; Yinpei Guo; Nan Yao; Han Wang; Bo Li (Biological Trace Element Research, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

Impacts of native vegetation on the hydraulic properties of the concentrated flows in bank gullies - Zheng-an Su; Zhou-yao He; Tao Zhou; Jun-jie Wang; Xiao-yi Wang; Li-juan Wang; Hai-dong Fang; Liang-tao Shi; Yi-han Liu; Zuo Wu (Journal of Mountain Science, 2021)

Isolation and preliminary functional characterization of MxWRKY64, a new WRKY transcription factor gene from Malus xiaojinensis Cheng et Jiang - Deguo Han; Jiaxin Han; Tianlong Xu; Tiemei Li; Chunya Yao; Yijia Wang; Dejia Luo; Guohui Yang (In Vitro Cellular & Developmental Biology - Plant, 2021)

Adaptive T cell immunotherapy in cancer - Dongdong Ti; Miaomiao Bai; Xiaolei Li; Jianshu Wei; Deyun Chen; Zhiqiang Wu; Yao Wang; Weidong Han (Science China Life Sciences, 2021)

Transcriptional and post-transcriptional regulation of the miR171-LaSCL6 module during somatic embryogenesis in Larix kaempferi - Qiao-Lu Zang; Yao Zhang; Su-Ying Han; Wan-Feng Li; Li-Wang Qi (Trees, 2021)
Key message Expression analysis of Larix kaempferi mature miR171s and their primary transcripts and target gene LaSCL6 during somatic embryogenesis revealed the transcriptional and post-transcriptional regulation of the miR171- LaSCL6 module. Abstract Somatic embryogenesis provides a useful experimental system for studying the regulatory mechanisms of plant development. The level and activity of microRNA171 (miR171) fluctuate during somatic embryogenesis in Larix kaempferi , but the underlying mechanisms are still unclear. Here, in L. kaempferi we identified five members of the miR171 family, which cleave LaSCL6 mRNA at different sites. In addition, we improved the method of measuring miRNA activity in a more direct way. Furthermore, we measured the expression patterns of mature miR171s and their primary transcripts during somatic embryogenesis in L. kaempferi and found that their patterns differed, indicating that the transcription of MIR171 genes and the subsequent cleavage of their intermediate products are regulated. Taken together, our findings not only offer a means to study the regulation of miRNA activity, but also provide further insight into the regulation of L . kaempferi somatic embryogenesis by miR171- LaSCL6 .

Pathological matrix stiffness promotes cardiac fibroblast differentiation through the POU2F1 signaling pathway - Mingzhe Li; Jimin Wu; Guomin Hu; Yao Song; Jing Shen; Junzhou Xin; Zijian Li; Wei Liu; Erdan Dong; Ming Xu; Youyi Zhang; Han Xiao (Science China Life Sciences, 2021)

Study on the Triaxial Unloading Creep Mechanical Properties and Damage Constitutive Model of Red Sandstone Containing a Single Ice-Filled Flaw - Ren-liang Shan; Yao Bai; Yang Ju; Tian-yu Han; Hao-yu Dou; Zhao-long Li (Rock Mechanics and Rock Engineering, 2021)

Sodium alginate/collagen hydrogel loaded with human umbilical cord mesenchymal stem cells promotes wound healing and skin remodeling - Zhenkun Zhang; Zhe Li; Ya Li; Yingying Wang; Minghao Yao; Kun Zhang; Zhenyu Chen; Han Yue; Jijing Shi; Fangxia Guan; Shanshan Ma (Cell and Tissue Research, 2021)

Detailed mapping of the surface rupture of the 12 February 2014 Yutian Ms7.3 earthquake, Altyn Tagh fault, Xinjiang, China - Zhaode Yuan; Jing Liu-Zeng; Xue Li; Jing Xu; Wenqian Yao; Longfei Han; Tao Li (Science China Earth Sciences, 2021)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

Rhodobacter xinxiangensis sp. nov., isolated from pakchoi-cultivated soil contaminated with heavy metal and its potential to reduce Cd and Pb accumulation in pakchoi (Brassica campestris L.) - Hui Han; Tiejun Wang; Zhaojin Chen; Yadong Li; Lunguang Yao (Archives of Microbiology, 2020)

Experimental study of failure characteristics and fissure propagation in hydrous siltstone - Liqiang Yu; Qiangling Yao; Xuehua Li; Weinan Wang; Hao Han; Mengting Zhang (Arabian Journal of Geosciences, 2020)

Shortened snRNA promoters for efficient CRISPR/Cas-based multiplex genome editing in monocot plants - Yu Hao; Wubei Zong; Dongchang Zeng; Jingluan Han; Shuifu Chen; Jianian Tang; Zhe Zhao; Xiaojuan Li; Kun Ma; Xianrong Xie; Qinlong Zhu; Yuanling Chen; et al. (Science China Life Sciences, 2020)

Evaluation of the relationship between DNA methylation status and heterosis in soybean with MethylRAD technique - Baixing Song; Yuanqian Wang; Songnan Yang; Xueying Li; Xiao Han; Sujie Fan; Abraham Lamboro; Dan Yao; Jing Qu; Zhuo Zhang; Yang Song; Jun Zhang (Euphytica, 2020)

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)

Activation of Sigma-1 Receptor Enhanced Pericyte Survival via the Interplay Between Apoptosis and Autophagy: Implications for Blood–Brain Barrier Integrity in Stroke - Yuan Zhang; Xiaotian Zhang; Qiangqiang Wei; Shuo Leng; Cai Li; Bing Han; Ying Bai; Huibin Zhang; Honghong Yao (Translational Stroke Research, 2020)

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

Isolation of urease-producing bacteria and their effects on reducing Cd and Pb accumulation in lettuce (Lactuca sativa L.) - Tiejun Wang; Shilin Wang; Xingchun Tang; Xianpeng Fan; Sheng Yang; Lunguang Yao; Yadong Li; Hui Han (Environmental Science and Pollution Research, 2020)

Anomalies and genetic mechanism of ethane carbon isotope in the Ordovician carbonate reservoirs in the Jingbian gas field, Ordos Basin, China - Wen-xue Han; Xiang-chun Chang; Shi-zhen Tao; Wei-wei Yang; Jing-li Yao (Carbonates and Evaporites, 2020)

Paleoseismologic record of earthquakes along the Wuzunxiaoer section of the Altyn Tagh fault and its implication for cascade rupture behavior - Zhaode Yuan; Jing Liu-Zeng; You Zhou; Zhigang Li; Heng Wang; Wenqian Yao; Longfei Han (Science China Earth Sciences, 2020)

Sanitary landfill improved CNPS microbial functional gene abundance compared to non-sanitary landfill - Yuzhen Luo; Weiwei Zhang; Yaying Li; Yongjie Wang; Huaiying Yao; Jigang Han (Journal of Soils and Sediments, 2020)

Integrated 3D bioprinting-based geometry-control strategy for fabricating corneal substitutes - Bin Zhang; Qian Xue; Han-yi Hu; Meng-fei Yu; Lei Gao; Yi-chen Luo; Yang Li; Jin-tao Li; Liang Ma; Yu-feng Yao; Hua-yong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Prediction of exploration targets based on integrated analyses of source rock and simulated hydrocarbon migration direction: a case study from the gentle slope of Shulu Sag, Bohai Bay Basin, northern China - Changqing Ren; Fugui He; Xianzhi Gao; Dongsheng Wu; Wenli Yao; Jianzhang Tian; Huiping Guo; Yuanxin Huang; Li Wang; Han Feng; Junwei Li (Geosciences Journal, 2019)

A biomimetic experimental study of magnesium ion mineralization in Mg-enriched aragonite - Qizhi Yao; Yuying Wang; Yifan Zhang; Han Li; Gentao Zhou (Science China Earth Sciences, 2019)

The occurrence of polybrominated diphenyl ether (PBDE) contamination in soil, water/sediment, and air - Zhineng Wu; Wei Han; Xin Yang; Yao Li; Yingying Wang (Environmental Science and Pollution Research, 2019)

A new prediction model of daily weather elements in Hainan province under the typhoon weather - Ruixu Zhou; Wensheng Gao; Bowen Zhang; Qinzhu Chen; Yafeng Liang; Dong Yao; Laijun Han; Xinzheng Liao; Ruihai Li (Meteorology and Atmospheric Physics, 2019)

Abnormalities of regional homogeneity and its correlation with clinical symptoms in Naïve patients with first-episode schizophrenia - Xiaoxin Zhao; Jingjing Yao; Yiding Lv; Xinyue Zhang; Chongyang Han; Lijun Chen; Fangfang Ren; Zhuma Jin; Yuan Li; Yuxiu Sui (Brain Imaging and Behavior, 2019)

Research on the electrostatic characteristic of coal-fired fly ash - Liqiang Qi; Yuan Yao; Tianyi Han; Jintao Li (Environmental Science and Pollution Research, 2019)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

The complete mitochondrial genome of Myanmar warty newt Tylototriton shanorum (Salamandridae: Tylototriton) - Mingwang Zhang; Ye Jiang; Fuyao Han; Qingyong Ni; Ying Li; Yongfang Yao; Huailiang Xu (Conservation Genetics Resources, 2018)

The entire mitochondrial genome of Vietnam Warty Newt Paramesotriton deloustali (Salamandridae: Paramesotriton) with a new distribution record from China - Mingwang Zhang; Fuyao Han; Jiang Ye; Qingyong Ni; Ying Li; Yongfang Yao; Huailiang Xu (Conservation Genetics Resources, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Myxovirus resistance protein A inhibits hepatitis C virus replication through JAK-STAT pathway activation - Hailong Wang; Xiu Xin; Mingzhen Wang; Lingling Han; Jiadai Li; Yao Hao; Congyi Zheng; Chao Shen (Archives of Virology, 2018)

Study on the relationship between genetic variation of DNA methylation and heterosis in soybean leaves - Yuanqian Wang; Kaixin Zhang; Lifang Sun; Xiao Han; Sujie Fan; Xueying Li; Yiwei Qu; Dan Yao; Piwu Wang; Jun Zhang (Euphytica, 2018)

Assessing the Photocatalytic Reduction of Cr(VI) by CuO in Combination with Different Organic Acids - Ying Li; Cheng Chen; Yao Wu; Yijie Han; Yeqing Lan (Water, Air, & Soil Pollution, 2017)

The complete mitogenome sequence of Tylototriton ziegleri (Amphibia: Caudata) - Ye Jiang; Zhimin Wei; Fuyao Han; Qingyong Ni; Yongfang Yao; Huailiang Xu; Ying Li; Dingqi Rao; Mingwang Zhang (Conservation Genetics Resources, 2017)

Seasonal variations and source apportionment of atmospheric PM2.5-bound polycyclic aromatic hydrocarbons in a mixed multi-function area of Hangzhou, China - Hao Lu; Shengsheng Wang; Yun Li; Hui Gong; Jingyi Han; Zuliang Wu; Shuiliang Yao; Xuming Zhang; Xiujuan Tang; Boqiong Jiang (Environmental Science and Pollution Research, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Dimethyl Fumarate and Monomethyl Fumarate Promote Post-Ischemic Recovery in Mice - Yang Yao; Weimin Miao; Zhijia Liu; Wei Han; Kaibin Shi; Yi Shen; Handong Li; Qiang Liu; Ying Fu; DeRen Huang; Fu-Dong Shi (Translational Stroke Research, 2016)

Preliminary studies of multi-micro/nanomaterials immobilized on the bamboo timber surface - Chunde Jin; Jingpeng Li; Jin Wang; Huanhuan Zheng; Qingfeng Sun; Shenjie Han; Chenye Yan; Qiufang Yao; Bitao Fan (Journal of the Indian Academy of Wood Science, 2016)

MiR-449a regulates autophagy to inhibit silica-induced pulmonary fibrosis through targeting Bcl2 - Ruhui Han; Xiaoming Ji; Rong Rong; Yan Li; Wenxi Yao; Jiali Yuan; Qiuyun Wu; Jingjin Yang; Weiwen Yan; Lei Han; Baoli Zhu; Chunhui Ni (Journal of Molecular Medicine, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Valuation of debris flow mitigation measures in tourist towns: a case study on Hongchun gully in southwest China - Ming-li Chen; Gui-sheng Hu; Ning-sheng Chen; Cun-yao Zhao; Song-jiang Zhao; Da-wei Han (Journal of Mountain Science, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

3D modeling of geological anomalies based on segmentation of multiattribute fusion - Zhi-Ning Liu; Cheng-Yun Song; Zhi-Yong Li; Han-Peng Cai; Xing-Miao Yao; Guang-Min Hu (Applied Geophysics, 2016)

Chimeric antigen receptor-modified T cells for the immunotherapy of patients with EGFR-expressing advanced relapsed/refractory non-small cell lung cancer - Kaichao Feng; Yelei Guo; Hanren Dai; Yao Wang; Xiang Li; Hejin Jia; Weidong Han (Science China Life Sciences, 2016)

A novel TaSST gene from wheat contributes to enhanced resistance to salt stress in Arabidopsis thaliana and Oryza sativa - Yao Li; Wenji Liang; Jie Han; Zhanjing Huang (Acta Physiologiae Plantarum, 2016)

An analytical biomarker for treatment of patients with recurrent B-ALL after remission induced by infusion of anti-CD19 chimeric antigen receptor T (CAR-T) cells - Yajing Zhang; Wenying Zhang; Hanren Dai; Yao Wang; Fengxia Shi; Chunmeng Wang; Yelei Guo; Yang Liu; Meixia Chen; Kaichao Feng; Yan Zhang; Chuanjie Liu; et al. (Science China Life Sciences, 2016)

Protection of Luteolin-7-O-Glucoside Against Doxorubicin-Induced Injury Through PTEN/Akt and ERK Pathway in H9c2 Cells - Hong Yao; Zhimei Shang; Penghong Wang; Shuixian Li; Qianyun Zhang; Huiqin Tian; Dongmei Ren; Xiuzhen Han (Cardiovascular Toxicology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Overexpression of d-amino acid oxidase from Bradyrhizobium japonicum, enhances resistance to glyphosate in Arabidopsis thaliana - Hongjuan Han; Bo Zhu; Xiaoyan Fu; Shuanghong You; Bo Wang; Zhenjun Li; Wei Zhao; Rihe Peng; Quanhong Yao (Plant Cell Reports, 2015)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Partial Volume Correction for Equivocal Retropharyngeal Nodal Metastases of Nasopharyngeal Carcinoma with Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography - Yu-Wen Wang; Chin-Shun Wu; Chih-Han Chang; Kuo-Sheng Cheng; Yu-Kang Chang; I-Wen Huang; Chin-Li Lu; Wei-Jen Yao (Journal of Medical and Biological Engineering, 2015)

Improving N1 classification by grouping EEG trials with phases of pre-stimulus EEG oscillations - Li Han; Zhang Liang; Zhang Jiacai; Wang Changming; Yao Li; Wu Xia; Guo Xiaojuan (Cognitive Neurodynamics, 2015)

Tobacco rattle virus mediated gene silencing in strawberry plants - Ji Tian; Li Cheng; Zhen-yun Han; Yun-cong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Application of aircraft observations over Beijing in cloud microphysical property retrievals from CloudSat - Lei Wang; Chengcai Li; Zhigang Yao; Zengliang Zhao; Zhigang Han; Qiang Wei (Advances in Atmospheric Sciences, 2014)

Pluripotent-related gene expression analyses in single porcine recloned embryo - Yongye Huang; Wanhua Xie; Chaogang Yao; Yang Han; Guangyun Tan; Yang Zhou; Jianguo Zhu; Daxin Pang; Zhanjun Li; Xiaochun Tang (Biotechnology Letters, 2014)

Impact of long-term application of manure, crop residue, and mineral fertilizer on organic carbon pools and crop yields in a Mollisol - Xueli Ding; Yaru Yuan; Yao Liang; Lujun Li; Xiaozeng Han (Journal of Soils and Sediments, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Generation of AQP2-Cre transgenic mini-pigs specifically expressing Cre recombinase in kidney collecting duct cells - Weiwei Luo; Zhanjun Li; Yongye Huang; Yang Han; Chaogang Yao; Xinping Duan; Hongsheng Ouyang; Li Li (Transgenic Research, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Monocyte to macrophage differentiation-associated (MMD) positively regulates ERK and Akt activation and TNF-α and NO production in macrophages - Qiang Liu; Jin Zheng; Dan-Dan Yin; Jie Xiang; Fei He; Yao-Chun Wang; Liang Liang; Hong-Yan Qin; Li Liu; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

RNASEL −1385G/A polymorphism and cancer risk: a meta-analysis based on 21 case–control studies - Li-Feng Zhang; Yuan-Yuan Mi; Chao Qin; Yong Wang; Qiang Cao; Jun-Feng Wei; Yao-Jun Zhou; Ning-Han Feng; Wei Zhang (Molecular Biology Reports, 2011)

An integrated drug-likeness study for bicyclic privileged structures: from physicochemical properties to in vitro ADME properties - Chunyan Han; Jinlan Zhang; Mingyue Zheng; Yao Xiao; Yan Li; Gang Liu (Molecular Diversity, 2011)

Interferon gamma +874 T/A polymorphism contributes to cancer susceptibility: a meta-analysis based on 17 case–control studies - Yuan-Yuan Mi; Qian-Qian Yu; Bin Xu; Li-Feng Zhang; Zhi-Chao Min; Li-Xin Hua; Ning-Han Feng; Yong Yao (Molecular Biology Reports, 2011)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Genetic diversity in Chinese sorghum landraces revealed by chloroplast simple sequence repeats - Ruyu Li; Han Zhang; Xincheng Zhou; Yanan Guan; Fengxia Yao; Guoan Song; Jiancheng Wang; Chunqing Zhang (Genetic Resources and Crop Evolution, 2010)

Numerical simulation of typhoon surges along the coast of Taiwan - Hsien-Wen Li; Cheng-Han Tsai; Yao-Tsai Lo (Natural Hazards, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Sesquilignans and dilignans from Campylotropis hirtella (Franch.) Schindl. - Hui-Ying Han; Hong-Wei Liu; Nai-Li Wang; Xin-Sheng Yao (Natural Product Research, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Total Internal Reflection Fluorescence Spectroscopy for Investigating the Adsorption of a Porphyrin at the Glass/Water Interface in the Presence of a Cationic Surfactant Below the Critical Micelle Concentration - Yao-Ji Tang; Ying Chen; Min-Na Yao; Zhe-Xiang Zou; Guo-Bin Han; Yao-Qun Li (Journal of Fluorescence, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Heat shock proteins and p53 play a critical role in K+ channel-mediated tumor cell proliferation and apoptosis - Xiaobing Han; Fang Wang; Weixing Yao; Hui Xing; Danhui Weng; Xiaohong Song; Gang Chen; Ling Xi; Tao Zhu; Jianfeng Zhou; Gang Xu; Shixuan Wang; et al. (Apoptosis, 2007)

Molecular cloning and overexpression of a novel UDP-glucosyltransferase elevating salidroside levels in Rhodiola sachalinensis - Lan-Qing Ma; Ben-Ye Liu; Dong-Yao Gao; Xiao-Bin Pang; Shi-You Lü; Han-Song Yu; Hong Wang; Fang Yan; Zhen-Qiu Li; Yan-Fang Li; He-Chun Ye (Plant Cell Reports, 2007)

Biodesulfurization of dibenzothiophene by growing cells of Gordonia sp. in batch cultures - Wei Li; Miao-Dong Wang; Han Chen; Jian-Meng Chen; Yao Shi (Biotechnology Letters, 2006)

Meta-analysis of the association of CTLA-4 exon-1 +49A/G polymorphism with rheumatoid arthritis - Shizhong Han; Yao Li; Yumin Mao; Yi Xie (Human Genetics, 2005)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)